Covalent coupling of myofibrillar protein–6-gingerol: Binding sites, alterations in protein structure and gel properties - Jiamei Li; Geyi Ren; Jiaqi Sun; Fei Li; Hongzhao Zhang; Ping Han; Shiling Lu; Juan Dong (Journal of Food Engineering, 2027)

Foam separation and coupled technologies in food industry: a review - Qing Li; Zhijie Guan; Mengting Gu; Tong Chen; Jiacong Wu; Lei Wang; Yun Wang; Juan Han (Journal of Food Engineering, 2027)

Prevalence of Klebsiella pneumoniae in raw milk and biocontrol potential of phage vB_Kpn_18-1 - Ting Qin; Xinyan Yao; Dai Peng; Chaoxiang Jia; Linlin Huang; Yingqian Han; Yanbin Yang; Yang Liu; Guoyu Yang; Juan Geng; Yueying Wang; Heping Li (International Dairy Journal, 2026)

Biological and genomic characteristics of a polyvalent Salmonella phage and its dual application in food decontamination and chick salmonellosis treatment - Xinyan Yao; Sijia Luo; Jinghao Xie; Chaoxiang Jia; Yingqian Han; Yanbin Yang; Yueting Zheng; Jiajia Pan; Juan Geng; Yueying Wang; Heping Li (Food Research International, 2026)

A synergistic enzymatic strategy for comprehensive improvement of bread quality and digestibility using a novel maltohexaose-forming amylase and a 4,6-α-glucanotransferase - Yu-chuan Wang; Hong Liu; Li-xiao Fu; Meng-jun Han; Qiao-juan Yan; Zheng-qiang Jiang; Yan-xiao Li (Food Hydrocolloids, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Sustainable extraction and in situ separation of bromelain from pineapple peel using deep eutectic solvent/salt system: molecular mechanism, hydrolytic activity and stability - Yiling Liu; Qizhen Huang; Yihan Liu; Jiacong Wu; Ming Li; Yun Wang; Juan Han; Lei Wang (Food Research International, 2026)

Deep placement of reduced nitrogen input strengthens soil water–nitrogen coupling and root–shoot coordination to enhance grain yield in dryland maize - Fu Liu; Jing Ling; Lan Luo; Xiaozhou Li; Yunfei Ren; Yi Zhou; Xiangyang Zhao; Xiaogang Yin; Shikun Sun; Juan Han; Youcai Xiong; Yuncheng Liao; et al. (Field Crops Research, 2026)

Protein network on reticular heterostructure for competitive organic photoelectrochemical transistor biosensing - Bo-Han Kou; Peiying Yin; Miao-Hua Chen; Hai-Yan Wang; Zheng Li; Wei-Wei Zhao; Jing-Juan Xu (Analytica Chimica Acta, 2026)

Plant litter enhances hexabromocyclododecane removal in riparian zones at high water level: Insights from the coupling of microbial dehalogenation and carbon cycling - Rong Wang; Juan Chen; Li Wang; Han Gao; Qihao Nie; Shunqing Zhang; Qiming He (Water Research, 2026)

Cadmium induced ferroptosis of TM4 cells through PERK-ATF4-CHOP signaling pathway - Xuan Li; Juan Dai; Jiaoyang Wei; Yan He; Yue Han; Ting Zhou; Rui Li; Ling Zhang; Yuqin Shi (Reproductive Toxicology, 2026)

Microbial and environmental determinants of 1-propanol biosynthesis in Jiang-flavor Baijiu fermentation - Wei-Tao Zhai; Han Zhao; Li-Juan Chai; Wei Zhang; Xiao-Juan Zhang; Zhen-Ming Lu; Chuan-Qiang Gao; Guan-Ru Si; Wen-Qing Zhang; Song-Tao Wang; Cai-Hong Shen; Zheng-Hong Xu (Food Microbiology, 2026)

On-site AFB1 detection in food via dual-gated system and Zn2+-doped UCNPs embedded in injectable PGB hydrogel - Yu Wu; Arul Murugesan; Yaru Han; Juan Han; Yiping Chen; Huanhuan Li (Chemical Engineering Journal, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Integrated transporter engineering and metabolic flux redistribution for efficient production of 3-fucosyllactose in Escherichia coli - Ruoyu Jia; Mengli Li; Mo Han; Juan Zhang; Ming Miao; Tao Zhang (Food Bioscience, 2026)

Whole-genome analysis and probiotic-related phenotypic characterization of the antifungal Lactiplantibacillus plantarum L6 isolated from traditional Chinese paocai - Saihui Sui; Yu Gao; Tianshuai Yuan; Yu Duan; Han Sun; Baokun Li; Juan Dong; Hua Ji; Cailan Wu (Food Bioscience, 2026)

Coupling microbial electrosynthesis and chain elongation for simultaneous biomethane upgrading and carboxylate recovery: A tunable carbon valorization strategy - Kai-Kai Wu; Shu-tong Wu; Chuan Chen; Zi-Han Wang; Ya-Ru Wang; Li Zhao; Juan Tong; Fei Shen; De-Feng Xing; Nan-Qi Ren; Lei Zhao (Water Research, 2026)

Plant-specific groundwater source apportionment and health risk assessment of chemical industrial parks based on an enhanced potential pollution index framework - Junjie Li; Jingjing Yu; Bin Yang; Ping Du; Chunmei Han; Juan Chen; Bei Yuan; Yunhui Zhang; Ruibing Han; Wenxuan Fan (Journal of Hazardous Materials, 2026)

Notable impact of urban ventilation corridors on the transport of particle-bound ultrashort-chain perfluoroalkyl substances in the atmosphere - Anen He; Feifei Li; Juan Li; Fanghan Sun; Han Fang; Xu Sun; Yanli Guo; Hailin Wang; Yawei Wang; Guibin Jiang (Journal of Hazardous Materials, 2026)

Cholesteryl ester accumulation as a biomarker for personalized selection of fertility-preserving therapies in endometrioid endometrial carcinoma - Yijiao He; Shenyi Yin; Wenying Zhao; Yanmin Wang; Danhua Shen; Yi Wang; Jing Geng; Xiaobo Zhang; Ying Yu; Juan Li; Yang He; Jiaxin Li; et al. (Science Bulletin, 2026)

Cultivar-specific divergence in volatile aroma profiles of heat-stressed grapes uncovered via GC×GC-TOFMS - Chenlu Du; Xinrui Liu; Minying Liu; Mingzheng Han; Zhen Zhang; Yuanyuan Xu; Yue Song; Yuanxu Teng; Dongying Fan; Junpeng Li; Lujia Wang; Juan He; et al. (Food Chemistry, 2026)

Structure–function relationships in chitosan films containing ZIF-8-confined Ligusticum jeholense essential oil: pH-triggered release and apple ring rot control - Xiao-Yi Tong; Yun-Feng Liu; Zhi-Hong Xu; Wan Li; Long-Fei Li; Li Han; Li-Juan Wang; Hong-De An; Fei Cao (Food Chemistry, 2026)

Optimal combination of iron/magnesium salts and urea can promote the degradation rate of maize straw by catalyzing the rapid de-polymerization of lignin - Han Li; Yuan fang Zhou; Sen Zhao; Si hui Yan; Ding hua Jia; Yan ping Zhang; Xiang dong Yang; Juan Li (Biocatalysis and Agricultural Biotechnology, 2026)

Genome-wide association analysis identifies novel genetic loci and candidate genes associated with seed dormancy in cultivated peanut - Maoning Zhang; Ziqi Sun; Feiyan Qi; Pei Du; Li Qin; Chenyu Li; Juan Wang; Chenyang Zhi; Jing Xu; Hua Liu; Zhiyuan Zhou; Lijuan Miao; et al. (Theoretical and Applied Genetics, 2026)

KDM3A Modulates Trastuzumab Resistance in HER2− Positive Breast Cancer Cells via the PI3K/AKT/ERK Pathway - Yuanxing Han; Jiayi Guo; Ting Yang; Xuewen Liu; Honghuo Yan; Yuanzhang Li; Juan Yao (Biochemical Genetics, 2026)

Bimetallic CuTb2O2 nanozyme-enabled enzyme-luminophore-nanozyme electrochemiluminescence sensor for sensitive detection of xanthine - Hanyue Jiang; Juan Lu; Wenzhuo Wang; Pengfei Han; Guangping Ma; Jing Wang; Li Tian; Tengying Ma (Food Chemistry, 2026)

Enhancing emulsion stability and whipping properties in recombined creams: Glycosylated casein conjugates for clean-label applications - Hongjuan Li; Kuan Liang; Juan Zhang; Feiyang Liu; Xin Wen; Aijia Han; Yaqi Qiu; Yongqiang Cao; Hongbo Li; Jinghua Yu (Food Hydrocolloids, 2026)

Coordination-encoded natural strong metal–support interaction for stabilizing Cu single-atom catalysts in lithium–sulfur batteries - Zhaoyang Han; Xiaotong Niu; Xinwei Guan; Tianci Ma; Minglei Jia; Juan Lian; Yan Li; Jinwei Mao; Bing Wang; Dawei Yang; Hangqi Yang; Fengzhu Ren; et al. (Chemical Engineering Journal, 2026)

Study on S-wave Velocity Structure and Seismogenic Structure in the Source Region of the 1976 M6.2 Horinger Earthquake - Dong-yang Pei; Xiao-ming Han; Juan Li; Fan Zhang; Li-feng Chen; Shu-bo Wang; Wei Guo; Xin Wang; Tie-suo Zhao; Xing Zhao; Jin-zhe Bao (Applied Geophysics, 2026)

Engineered high-crystallinity iron oxides suppress iron reduction competition and enhance anaerobic digestion methane yield via direct interspecies electron transfer - Yi Han; Zhengke Li; Xiejuan Lu; Juan Mao; Xiaohui Wu; Feixiang Zan (Journal of Environmental Chemical Engineering, 2026)

In-situ construction of novel dual bismuth–rich Bi4O5Br2/Bi7O9I3 S-scheme heterojunction with enhanced photocatalytic activity for degradation of diverse persistent organic pollutants - Jia-Lin Zong; Hui-Long Wang; Hao Huang; Yi-Hui Zhao; Li-Juan Han; Wen-Feng Jiang (Journal of Environmental Chemical Engineering, 2026)

Antimicrobial mechanism of green citrus peel extract against Gluconobacter cerinus causing decay in ‘Xuxiang’ kiwifruit - Juan Xie; Giri Raj Tripathi; Zhangxing Li; Hongyu Li; Xiaobo Liang; Peng Han; Ge Zhao; Miaomiao Yang (International Journal of Food Microbiology, 2026)

A mutation in CsBRP1, encoding a PHD-type domain-containing protein, causes semi-dwarfism in cucumber (Cucumis sativus L.) - Xiaoxu Han; Juan Yin; Xueying Jiao; Ruolin Hu; Yingjie Zhang; Fahang Chen; Biao Dong; Chunyan Cheng; Yuhui Wang; Chunhua Wang; Ji Li; Tao Wu; et al. (Theoretical and Applied Genetics, 2026)

Spatiotemporal variations in indoor thermal environments and dynamic comfort of passengers in airport terminals during winter - Yuxin Yang; Juan Yu; Deyin Zhang; Hao Tang; Wenzhong Jiang; Libin Han; Junmin Li; Borong Lin; Yu Dong (Building and Environment, 2026)

Root microorganisms enhance crop resistance to low-temperature stress by increasing antioxidant enzyme activity - Han Zhang; Junhui Li; Gang Chen; Youguo Zhan; Dekai Ning; Jiaqi Liu; Ruiwen Hu; Ge Tan; Qiyun Zhou; Juan Li; Zhengling Liu (Planta, 2026)

A mixed mushroom poisoning in humans associated with the ingestion of Collybiopsis orientisubnuda - Xiu-Juan Li; Chang Xu; Wen-Hao Zhang; Jing Ma; Han-Chi Lei; Jia Li; Yu-Xian Gao; Xing Xia; Ping Wei; Yi Liu; Li-Ping Tang (Toxicon, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Associations of paraben exposures measured by repeated urinary biomarkers with sperm DNA damage and apoptosis - Xiu-Ting Li; Yu Miao; Min Zhang; Jia-Yue Zeng; Peng-Hui Liu; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; Ning Zhang; Long Ge; Han-Qin Ye; Pan-Pan Chen; et al. (Environmental Research, 2026)

Prenatal organophosphate esters exposure impacts placental structure and inflammatory markers in a trimester-specific manner - Yuan Liu; Ping Lv; Xing Wang; Mengqian Zhang; Yifan Wang; Sheng Wang; Mengjuan Lu; Han Li; Hong Gan; Juan Tong; Hui Gao; Fangbiao Tao (Environmental Research, 2026)

Deep Subdomain Adaptation Network for Three-Dimensional Mineral Prospectivity Modeling with Imbalanced Data: A Case Study of the Damiao–Hongshila Fe–V–Ti Belt, China - Zhiqiang Zhang; Wenliang Chen; Emmanuel John M. Carranza; Wei Han; Xinxing Liu; Yingjie Li; Juan Zhang; Feng Li; Ziyang Lu; Yongjun Su; Gongwen Wang (Natural Resources Research, 2026)

Characterization and production optimization of genistein by the novel endophytic fungus Aspergillus sydowii J11 isolated from pigeon pea (Cajanus cajan) and its antibacterial and antioxidant properties - Bin-bin Li; Xuexia Gao; Min Lv; Wen-juan Ning; Jing-tao Liang; Xin-yu Fan; Xin-ming Lv; Jin-feng Song; Xiao-han Yuan; Cheng-bo Gu (Biotechnology Letters, 2026)

Isolation and antibacterial activity of three new flavonol compounds from Sophora flavescens - Si-Han Wang; Xiang-Yu Zhao; Zhi-Kang Chen; Yun Gao; Xin-Min Li; Ya-Juan Gao; Jing-Ming Jia; An-Hua Wang (Natural Product Research, 2026)

A mortise–tenon joint system facilitates precise targeted DNA insertion and replacement in rice - Wenjing Sun; Yaoyao Zhu; Xiuhua Zhang; Xiangbing Meng; Kai Xia; Xin Zhang; Xue Han; Wenbo Pan; Juan Guo; Jiayang Li; Huawei Zhang (Molecular Plant, 2026)

Dicyanoisophorone-based near-infrared fluorescent probe with a large Stokes shift for the detection and bioimaging of hydrazine - Hong-Cheng Xia; Yu-Hang Zhang; Li-Ming Lv; Di Han; Hong-Kun Yang; Hui-Juan Yan; Jie-Li Lv; Jun-Tang Lin; Ying-Ying Kong (Journal of Hazardous Materials, 2026)

Construction and application of a MASH-like liver organoid model reveals the metabolic modulatory effects of Angelica sinensis polysaccharide - Shiyi Tan; Yu-Han Cai; Wei Wang; Li Ma; Xulei Zuo; Tingting Xu; Haohan Liu; Yuxi Zhang; Hao Gao; Geyu Liang; Yuepu Pu; Zhongze Gu; et al. (Food Bioscience, 2026)

Pillar[5]arene cross-linked chitosan polymer with enhanced selective removal of toxic anionic dyes: Preparation, characterization, adsorption mechanism, and cytotoxicity assessment - Cheng-Nuo Hu; Suo-Luan Zhou; Yan Chen; Ming-Kun Yang; Yun-Han Yang; Zhen Zhang; Li-Juan Yang (Carbohydrate Polymers, 2026)

Polystyrene nanoparticles promote endometrial cancer progression via downregulation of UGT1A genes - Liping Zhang; Yueying Li; Xiaonan Cai; Guilin Hou; Han Xiao; Juan Du (Chemico-Biological Interactions, 2026)

Fusion of Multi-Source Evapotranspiration Products Via the Bayesian Three-Cornered Hat Method and its Application in Runoff Simulation for Semi-Arid Basins - Chuqiao Han; Jianghua Zheng; Wanqiang Han; Liang Liu; Congren Li; Wenjie Yu; Juan Yang; Jiale Wu (Water Resources Management, 2026)

Local Spatial Attention Transformer with First-Order Difference for Sea Level Anomaly Field Forecast: A Regional Study in the East China Sea - Yuting Wang; Hui Chen; Lifang Jiang; Qiyan Ji; Juan Li; Jianxin Wang; Guoqing Han (Journal of Marine Science and Engineering, 2025)
Accurate prediction of regional sea level anomaly (SLA) is critical for coastal hazard early warning, navigation safety, and infrastructure protection in economically active marginal seas such as the East China Sea (ECS), yet complex multiscale air–sea dynamics still make SLA forecasting challenging. This study proposes a Local Spatial Attention Transformer Network (LSATrans-Net) for short-term regional SLA prediction in the ECS, which incorporates a Local Spatial Attention mechanism designed for regional ocean processes and employs a first-order difference preprocessing strategy to reduce error accumulation induced by data non-stationarity. The LSATrans-Net outperforms ConvLSTM, BiLSTM, and CNN-Transformer in 7-day prediction experiments, with an RMSE of 0.017 m and a PCC of 0.984, with particularly strong forecasting skill in the ECS-Kuroshio and eddy-active regions. LSATrans-Net provides an efficient and physically interpretable framework for high-precision short-term SLA forecasting in dynamically complex marine regions, and offers reliable technical support for coastal disaster prevention and operational ocean forecasting systems.

Binding affinities of arsenic to environmental dissolved organic matter: Behavior differences of hydrophilic/phobic fractions and environmental implications - Ning-Xin Wang; Yi-Han Cheng; Yu-Lai Wang; Li-Juan Zhang; Jin Xu (Science of The Total Environment, 2025)

Temporal and spatial variations of redox conditions in the middle Triassic Chang 7 member of the Yanchang formation, Ordos Basin, North China - Hanlin Liu; Yuangeng Huang; Xiangdong Zhao; Wei Wang; Xincheng Qiu; Zhen Qiu; Juan Han; Zhen Shen; Yujie Li; Ganlin Hua; Zhong-Qiang Chen; Caineng Zou (Marine and Petroleum Geology, 2025)

A nanozyme-based dual-mode sensor for photoelectrochemical and colorimetric assay of Listeria monocytogenes - Mengjie Li; Tingting Han; Chunyue Xia; Juan Xu; Chong Sun; Jiahui Chen; Weimin Xu; Daoying Wang (Food Chemistry, 2025)

Facile and Rapid Synthesis of Cerium-Modified UiO-66-NH2 for Efficient Removal of Safranine T from Aqueous Solutions - Zhengjie Li; Chunxia Fang; Xilong Ma; Yixian Liu; Juan Xie; Pengfei Li; Zhikun Zhang; Xudong Zhao; Hua Sun; Jilong Han (Water Conservation Science and Engineering, 2025)

Hippocampal Extracellular Matrix Protein Laminin β1 Regulates Neuropathic Pain and Pain-Related Cognitive Impairment - Ying-Chun Li; Pei-Yang Liu; Hai-Tao Li; Shuai Wang; Yun-Xin Shi; Zhen-Zhen Li; Wen-Guang Chu; Xia Li; Wan-Neng Liu; Xing-Xing Zheng; Fei Wang; Wen-Juan Han; et al. (Neuroscience Bulletin, 2025)

Piezo1 in heart failure: A new perspective from cytomechanical sensing to diverse cellular pathways - Jia-yan Wang; Bo-han Li; Chang-yu Liu; Qian-he Wang; Jie Wang; Mao-juan Guo; Xi-juan Jiang (Molecular Biology Reports, 2025)

Role of mitochondrial metabolism in ischemic stroke and natural products intervention - Xuan-Hao Zhang; Ying Li; Cheng-Yu Jin; Jia-Le Zhang; Yang-Peng Yan; Jia-Xiu Guo; Xin Lu; Han-Qing Pang; Yong-Juan Zhao (Molecular Biology Reports, 2025)

Integrated Geology-Geophysics Exploration of Rare Metal Deposits in the Yidun Island Arc Collisional Orogen - Rong Yang; Yu Peng; Li Qing; Qian-kun Liu; Xue-feng Hao; Han Wu; Jun-bo Fan; Hong-juan Chen; Tao Yang (Applied Geophysics, 2025)

Unraveling Qu-aroma variation between inner and outer layers of medium-temperature Daqu: A multi-omics and sensory approach - Sheng-Bing Yang; Zhen-Ming Lu; Han-Jun Shen; Jun-Jie Fu; Yang Yang; Xiao-Juan Zhang; Li-Juan Chai; Song-Tao Wang; Su-Yi Zhang; Cai-Hong Shen; Jin-Song Shi; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Exploring protein-mediated quality control mechanisms in Rice cooking behavior: from static protein content to dynamic architecture - Mengdi Chen; Han Geng; Dong Wang; Jinhong Gou; Mingqin Li; Ting Li; Xinxia Zhang; Juan Li; Li Wang (Food Chemistry, 2025)

Metabolomic insights into pigment and bioactive metabolite alterations in Eucommia ulmoides leaves: A comparison between new variety and wild-type varieties - Tiannuo Hong; Jiayu Gu; Lu Chen; Xiaolu Wang; Libin Zhou; Xuehu Li; Wenke Bai; Linqi Gao; Xiaodong Li; Guangming Zhao; Juan Han; Luxiang Liu (Food Chemistry, 2025)

Peroxydisulfate intercalated Ni-Zn-Al layered double hydroxide for ciprofloxacin degradation: The synergistic effect of the radical pathway and the non-radical pathway - Yiqiong Yang; Yubin Zhang; Juan Han; Shujian Cai; Lun Xiao; Kaiquan Li; Xiaodong Zhang (Chemical Engineering Journal, 2025)

Cell membrane-inspired controllably degradable polyesters: High barrier and tailored oxidation responsiveness - Qingyang Luan; Xiaolin Duan; Han Hu; Jiayi Li; Kai Lu; Qi Gao; Xiaokun Hong; Dong-Qing Wei; Juan Li; Jinggang Wang; Jin Zhu (Chemical Engineering Journal, 2025)

Maternal placental growth factor mediates the association between PM2.5 and its constituents with adverse pregnancy outcomes - Yuanyuan Yu; Wenjun Fan; Jiayan Ni; Xiaoli Gao; Weixia Li; Jianqiong Zheng; Hongping Zhang; Juan Chen; Qisijing Liu; Zi Lin; Bin Chen; Yajuan Wang; et al. (Journal of Hazardous Materials, 2025)

How to quantify the impact of urban expansion on ecological security in Northwest China - Juan Yang; Jianghua Zheng; Binbin Lu; ChuQiao Han; Congren Li; Jiale Wu; Linzhi Han; Paul Harris (Journal of Cleaner Production, 2025)

Adaptive responses and molecular mechanisms of Lactiplantibacillus plantarum to citric acid stress - Han Xie; Wei Zhang; Cong-Rong Shi; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

Exploring the quality changes of carp roes: perspective from flavor characteristics and microstructure - Gaomin Han; Qiqi Li; Hui Hong; Juan You; Tao Yin; Shanbai Xiong; Ru Liu (Food Research International, 2025)

Identification and Functional Analysis of Trehalose Synthesis Genes in Foxtail Millet: Insights into Low-Temperature Stress Response - Yueyue Wang; Yajun Li; Yidan Luo; Yuhua Xu; Bo Zhao; Rong Sun; Juan Zhao; Xukai Li; Yijuan Zhang; Yuanhuai Han; Hongying Li; Hui Zhang (Journal of Plant Growth Regulation, 2025)

Endophytic Bacterium Paenibacillus illinoisensis Y11 Promotes Duckweed Growth and Enhances Cadmium Pollution Remediation - Zhi-Qun Chen; Ai-Juan Tan; Yi-Fei Wan; Yu-Han Dong; Xiao Yang; Gui-Li Yang (Current Microbiology, 2025)

A pumpkin seed vitality detection model based on deep spectral features - Weiming Shi; Hongfei Zhu; Miaomiao Lu; Juan Li; Zhongzhi Han (Computers and Electronics in Agriculture, 2025)

The avoidance response in plant root to the environmental pollutant triclosan - Lanlan Zheng; Lei You; Shiqi Wu; Shan He; Ke Ning; Jinlin Lei; Chenglin Wang; Guodong Wang; Huibin Han; Huailan Guo; Jing Wang; Yonghong Zhang; et al. (Journal of Hazardous Materials, 2025)

High-selectivity NIR biosensor and in vivo imaging for Hg2+ detection based on a DNA-wrapped single-chirality carbon nanotube - Lele Wang; Han Liu; Lanying Li; Ruiyan Guo; Xuefei Yang; Xiaoqian Chen; Yanli Wen; Meixia Cao; Juan Yan; Gang Liu (Journal of Hazardous Materials, 2025)

Diaporthein B/ZnO/chitosan biodegradable film for postharvest preservation of apples: Characterization and application - Hui-Fang Du; Fei Cao; Zhi-Hong Xu; Ya-Xian Gao; Ya-Hui Zhang; Sen Pang; Wan Li; Long-Fei Li; Li Han; Li-Juan Wang; Hong-De An (Food Packaging and Shelf Life, 2025)

Cucurbitacin B alleviates DSS-induced experimental colitis by targeting ZNF70 to suppress the NLRP3/STAT3 signaling axis - Shen Cao; Yuhan Wang; Yi Tai; Jing Han; Yanjin Zheng; Can Wang; Hong Xiang Zuo; Ming Yue Li; Yue Xing; Xuejun Jin; Juan Ma (Inflammopharmacology, 2025)

Novel L1A/C RFLP 1–3-4 porcine reproductive and respiratory syndrome virus causing severe intestinal infections in China - Bo Han; Yi-han Lu; Jiu-ying Sun; Xin-lei Li; Wen-juan Zhang; Xiao-xue Yu; Gang Xu; Dao-wen Li; Xue-jiao Cheng; Chun-xue You; Ying-Feng Sun (Veterinary Microbiology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Cadmium induces autophagy via IRE1 signaling pathway activated by Ca2 + in GC-2spd cells - Yue Han; Juan Dai; Jinxin Cheng; Yan He; Chengkun Zhao; Rui Li; Yaqin Zhang; Ling Zhang; Ting Zhou; Yuqin Shi (Reproductive Toxicology, 2025)

Sex-and stage-specific effect of prenatal exposure to organophosphate esters with children's physical growth patterns and adiposity rebound timing: Modification by breastfeeding - Xing Wang; Juan Tong; Han Li; Mengjuan Lu; Yuan Liu; Hong Gan; Yifan Wang; Menglong Geng; Xuejiao Qie; Xiulong Wu; Hui Gao; Beibei Zhu; et al. (Journal of Hazardous Materials, 2025)

Separation of 99Tc by ion exchange martials: A critical review - Juan Tong; Beijia Chang; Binliang Li; YuanKun Liu; LiPeng Han; Kesheng Hu; Qi Zhao; Junqiang Yang; Keliang Shi; Xiaolin Hou (Journal of Environmental Chemical Engineering, 2025)

A resonance energy transfer electrochemiluminescence sensor based on the synergistic effect of luminol@β-cyclodextrin and Ni-MOF@Pt NPs for the oxytetracycline detection - Li Tian; Shuning Yang; Guangping Ma; Pengfei Han; Hanyue Jiang; Wenzhuo Wang; Juan Lu (Food Chemistry, 2025)

Structural design and solid electrolyte interphase modulation of SiOC-based anodes via N-doping for fast-charging lithium-ion batteries - Juan Wang; Yaqian Li; Siwen Jin; Xiuhui Zheng; Juncong Yuan; Debin Kong; Han Hu; Xiang Feng; De Chen (Chemical Engineering Journal, 2025)

Construction of hierarchical nanostructured surface on an organic hybrid selenidostannate with light trapping effect to achieve sunlight-driven environmental remediation - Ji-Ming Yu; Longfei Zhai; Bing Zheng; Haohao Li; Chunhui Hou; Yimin Han; Juan Ma; Zihui Wang; Wei-Wei Xiong (Journal of Hazardous Materials, 2025)

Electrochemiluminescence platform for curcumin detection based on g-C3N4 of N-rich vacancy and Ti2AlC - Yujia Song; Li Tian; Ruidan Li; Yanjia Guo; Pengfei Han; Guangping Ma; Hanyue Jiang; Wenzhuo Wang; Juan Lu (Food Chemistry, 2025)

Dual-potential ratiometric electrochemiluminescence platform based on PCN and Ti3CN@luminol for kanamycin detection in milk samples - Chao Li; Juan Lu; Yanjia Guo; Yujia Song; Ruidan Li; Hanyue Jiang; Wenzhuo Wang; Pengfei Han; Guangping Ma; Jing Wang; Li Tian (Food Chemistry, 2025)

Mixed-linker Zr-based metal-organic framework as a highly sensitive probe for ultrafast and selective detection of fluoride ions - Juan Chen; Tingting Guo; Hongyi Gao; Han Meng; Zhixin Zhang; Jie Li; Zhili Song; Xingyu Pei; Supakorn Boonyuen; Xiaowei Zhang; Yu Jiang; Jinzhang Tao (Environmental Research, 2025)

Nonclinical safety and biodistribution evaluation of HC009 mRNA vaccine against COVID-19 in rat - Juan Liu; Xicheng Chen; Chuanqian Chen; Jie Wu; Fengyang Xie; Jing Li; Huafeng Han; Yingying Zhao; Yongsheng Yang (Toxicology, 2025)

Optimizing the ratio of controlled release urea relative to normal urea to improve the crop yield and N recovery efficiency – A global meta-analysis - Shiju Liu; Yaru Zhang; Dehao Zhao; Yuncheng Liao; Guangxin Zhang; Yajun Li; Juan Han (Field Crops Research, 2025)

The mouse resource at National Resource Center for Mutant Mice of China - Bingzhou Han; Dongshen Chen; Zhong Chen; Ting Wang; Kaiyuan Zi; Rui Feng; Xiaoliu Yang; Ling’en Li; Juan Liang; Xiang Gao (Mammalian Genome, 2025)

Ozone-mediated carboxylation: a strategy for enhanced organic matter removal via in-situ crystallization of hardness ion - Keqian Li; Yujia Han; Yi Chen; Zhihao Fu; Heng Quan; Yadong Wang; Yabo Shang; Juan Shi; Pengkang Jin; Xin Jin (Journal of Cleaner Production, 2025)

Tough, antibacterial, and antioxidant chitosan-based composite films enhanced with proanthocyanidin and carvacrol essential oil for fruit preservation - Lijun Qian; Ruijing Jia; Quanling Zhao; Ningjing Sun; Juan Yang; Jialong Wen; Han Li; Jisheng Yang; Liuting Mo; Wei Gao; Shuduan Deng; Zhiyong Qin (Food Research International, 2025)

Lubricated injectable electroactive short fibers facilitate cartilage repair through piezoelectric conversion - Xiaoqian Ding; Jieliang Shen; Jindong Tan; Fan Wang; Weiwei Yi; Zijie Wang; Xinhe Li; Xinyu Zhang; Yi He; Wang Han; Mengtong Guan; Bo Liao; et al. (Chemical Engineering Journal, 2025)

Spatial adaptations in hospitality amid COVID-19: A case study of Xiamen's B&B sector - Juan Lin; Han Li; Shuyu Xing; Weiye Xiao (Applied Geography, 2025)

MiR-518b Promotes the Tumorigenesis of Hepatocellular Carcinoma by Targeting EGR1 to Regulate PI3K/AKT/mTOR Signaling Pathway - Xinyuan Wang; Juan Li; Jiao Nong; Xin Deng; Yiping Chen; Bing Han; Lin Zeng; Xiabing Huang (Cell Biochemistry and Biophysics, 2025)

Differences in Pathogenetic Mechanism Between Tibetan and Han High-Altitude Polycythemia Based on a Whole Genome-Wide Association Study - Zhuoma Basang; Shixuan Zhang; Xianwei Ke; Zhuoma Duoji; La Yang; Danzeng Qiangba; Yang De; Deji Gesang; Zixin Hu; Yanyun Ma; Meng Hao; Ruidong Fan; et al. (Phenomics, 2025)

Rice-fish co-culture promotes multiple ecosystem services supporting increased yields - Shuang-Xi Li; Jian Jiang; Wei-Guang Lv; Evan Siemann; Ben A. Woodcock; Yu-Quan Wang; Andrea Cavalieri; Na-Ling Bai; Juan-Qin Zhang; Xian-Qing Zheng; Han-Lin Zhang; Hai-Yun Zhang; et al. (Agriculture, Ecosystems & Environment, 2025)

Plasticization of gelatin/chitosan films with deep eutectic solvents and addition of Flos Sophora Immaturus extracts for high antioxidant and antimicrobial - Quanling Zhao; Xi Huang; Lijun Qian; Ningjing Sun; Juan Yang; Jialong Wen; Han Li; Jisheng Yang; Liuting Mo; Wei Gao; Zhiyong Qin (Food Hydrocolloids, 2025)

Extreme climate weakens the effect of biochar in increasing yield and reducing N2O emissions - Yeye Zhang; Ruixue Chen; Liru Yao; Chun Yan; Hongxia Li; Guangxin Zhang; Michael Bahn; Fei Mo; Juan Han (Field Crops Research, 2025)

Cadmium induces spontaneous abortion by impairing endometrial stromal cell decidualization - Xue-Ke Zhang; Xuan Li; Xing-Xing Han; Dong-Ying Sun; Yu-Qin Wang; Zi-Zhuo Cao; Lu Liu; Zi-Han Meng; Guo-Jing Li; Yu-Jie Dong; Dan-Yang Li; Xiao-Qing Peng; et al. (Toxicology, 2025)

Structure-rheological relationship of capillary protein oleogels: The role of particle wettability - Gao-Shang Wang; Long-Yuan Zhang; Guang-Xin Feng; Chuan-Wu Han; Li-Juan Wang; Jian Guo; Zhi-Li Wan; Xiao-Quan Yang (Food Hydrocolloids, 2025)

Controlled release urea combined with normal urea maintains the N balance and improves the environmental and economic benefits in wheat–maize multiple cropping - Shiju Liu; Yongqi Li; Yaru Zhang; Lijin Chen; Tao Wang; Hongxia Li; Yuncheng Liao; Yajun Li; Guangxin Zhang; Juan Han (European Journal of Agronomy, 2025)

Construction of S-scheme heterojunction based on an organic hybrid silver tin selenide with strong affinity to Cr(VI) for efficient photocatalytic Cr(VI) reduction - Ji-Ming Yu; Chunhui Hou; Wen-Bo Pei; Longfei Zhai; Haohao Li; Yimin Han; Zihui Wang; Juan Ma; Wei-Wei Xiong (Chemical Engineering Journal, 2025)

A new isoflavone from the stems of Derris eriocarpa How - Ying Liu; Zhen-Xin Zhu; Yue Lu; Cong Wang; Hong-Cun Liu; Juan Meng; Jin Qi; Xiao-Ning Huang; Xiao-Mei Lu; Wen-Sen Lu; Shu-Han Luo; Hai-Na Liang; et al. (Natural Product Research, 2025)

A telomere-to-telomere genome assembly of the cultivated peanut - Xiaobo Wang; Ziqi Sun; Feiyan Qi; Zhiyuan Zhou; Pei Du; Lei Shi; Wenzhao Dong; Bingyan Huang; Suoyi Han; Stefano Pavan; Meng Zhang; Mengjie Cui; et al. (Molecular Plant, 2025)

Fast photocatalytic Cr(VI) removal by an organic hybrid silver antimony sulfide coupled with PEDOT - Yimin Han; Longfei Zhai; Wen-Bo Pei; Jiahua Luo; Ji-Ming Yu; Haohao Li; Chunhui Hou; Zihui Wang; Juan Ma; Bing Hu; Wei-Wei Xiong (Journal of Cleaner Production, 2025)

Selective capture of iodine and toxic anionic dyes of a novel quaternary ammonium salt pillar[5]arene polymer with antibacterial activity - Yan Chen; Ming-Kun Yang; Suo-Luan Zhou; Cheng-Nuo Hu; Yun-Han Yang; Zhen Zhang; Li-Juan Yang (Chemical Engineering Journal, 2025)

Development of “environmentally friendly” super Escherichia coli strains that can completely biodegrade toluene - Yu Wang; Cen Qian; Yong-Dong Deng; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Yuan-Zhang Sun; Hong-Juan Han; Wen-Hui Zhang; Hao Zhang; et al. (Chemical Engineering Journal, 2025)

A novel ATP2A2 mutation in Darier and genotype phenotype: correlation analysis - Xiaofen Guo; Juan Du; Mingwei Lv; Yi Hu; Qi Zhen; Weiwei Chen; Yirui Wang; Zhuo Li; Chunmeng Liu; Xinyu Feng; Wanli Niu; Yu Zhang; et al. (Genes & Genomics, 2025)

Characterization of the complete genome of a novel allexivirus infecting Sauropus androgynus in China - Li-Juan Zhu; Lan-Yi Su; Xing Chen; Shifang Pan; Fagang Xia; Yan-Hong Han; Zhongtian Xu; Qian Xu (Archives of Virology, 2025)

Modification of gut and airway microbiota on ozone-induced airway inflammation - Fei Xu; Qiong Wu; Lin Yang; Han Sun; Juan Li; Zhen An; Huijun Li; Hui Wu; Jie Song; Wen Chen; Weidong Wu (Science of The Total Environment, 2024)

PM2.5-mediated cardiovascular disease in aging: Cardiometabolic risks, molecular mechanisms and potential interventions - Francis Chanda; Kai-xuan Lin; Abdallah Iddy Chaurembo; Jian-yuan Huang; Hui-juan Zhang; Wen-hui Deng; Yun-jing Xu; Yuan Li; Li-dan Fu; Hao-dong Cui; Chi Shu; Yang Chen; et al. (Science of The Total Environment, 2024)

Upgrading pyrolysis carbon black by recyclable ferrate/alkaline treatment with the assistance of ultrasound - Ke Liu; Zhengqing Kong; Yanchun Han; Liying Zhang; Juan Liu; Heyue Sun; Fangshuo Li; Shouke Yan; C.D. Midhun Dominic; Hao Wu; Lu Zong; Jianming Zhang; et al. (Journal of Cleaner Production, 2024)

Facile synthesis of geopolymer-based hierarchical porous materials for efficient adsorption-photocatalysis of dye wastewater - Han Xiao Su; Chan Juan Li; Yao Jun Zhang (Journal of Environmental Chemical Engineering, 2024)

A novel mutation in hERG gene associated with azithromycin-induced acquired long QT syndrome - Yun-Jiu Cheng; Yang Wu; Hui-Qiang Wei; Yi-Jian Liao; Li-Ping Qu; Yue-Han Pan; Li-Juan Liu; Wen-Tao Bi (Molecular Biology Reports, 2024)

Grazer‐induced toxin production is energetically costly and significantly reduces growth of cylindrospermopsin‐producing cyanobacteria - Lamei Lei; Wei Liu; Zihan Chen; Liang Peng; Li‐Juan Xiao; Bo‐Ping Han; Brett A. Neilan (Limnology and Oceanography, 2024)
Toxins have been proposed as a defense mechanism for phytoplankton against zooplankton grazing. However, the associated costs are not understood. Here, we aim to reveal the costs in terms of both physiological and molecular responses in the cylindrospermopsin (CYN)‐producing cyanobacterium Raphidiopsis raciborskii . Exposure of R. raciborskii to Daphnia magna resulted in a significant increase in its CYN cell quota which was grazer cell density‐dependent, indicating an inducible effect on CYN production. A negative and significant relationship between cellular growth rate and CYN production suggested a growth‐defense trade‐off, highlighting the costly nature of toxin production. Despite strong transcriptional responses (121 differentially expressed genes) in R. raciborskii under grazing pressure, the CYN gene cluster remained largely unaffected, implying post‐transcriptional regulation of CYN biosynthesis. Significant variation was observed in transcripts for phosphorus metabolism and photosynthesis‐related genes, and evidenced that energy (ATP) metabolic processes were stimulated. This study is the first to demonstrate the high energy requirements for CYN production and provide insight into the molecular basis underlying the costs of toxin production.

Microbial life-history strategies and particulate organic carbon mediate formation of microbial necromass carbon and stabilization in response to biochar addition - Yeye Zhang; Tao Wang; Chun Yan; Yuze Li; Fei Mo; Juan Han (Science of The Total Environment, 2024)

Millennial-scale sedimentary evolution of carbonate platforms during the Permian–Triassic boundary hyperthermal event - Jiawei He; Xiumian Hu; Juan Li; David B. Kemp; Mingcai Hou; Zhong Han (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Development of halochromic labels based on binary systems of cationic guar gum and κ-carrageenan loaded with alizarin red S for monitoring milk and seafood freshness - Jiaci Chen; Juan Zhang; Chuan Liu; Yumeng Sun; Xiaoxu Han; Xiaoyun Sun; Xiaoyan Pei; Fengchun Huang; Xiangyang Li; Ailiang Chen (Food Hydrocolloids, 2024)

Green massive mechanical synthesis of highly efficient Zn-Doped Cs3Cu2I5 for LED and X-ray imaging applications - Qi-Hua Yang; Gui-Hua Li; Yu-Chen Ao; Shu-Juan Zhao; Han-Qi Wei; Le Fu; Zhi-Wei Luo; Tian-Liang Zhou; Chu-Jie Wang; Ge-Mei Cai (Chemical Engineering Journal, 2024)

Shifts in reproductive strategies in the evolutionary trajectory of plant lineages - Xin-Jian Zhang; Xian-Han Huang; Jacob B. Landis; Quan-Sheng Fu; Jun-Tong Chen; Peng-Rui Luo; Li-Juan Li; Heng-Yi Lu; Hang Sun; Tao Deng (Science China Life Sciences, 2024)

Acacetin targets STING to alleviate the destabilization of the medial meniscus-induced osteoarthritis in mice - Dingjun Xu; Linjie Zhang; Chenyu Song; Dinglei Zhang; Chunlei Xing; Juan Lv; Huihui Bian; Minyu Zhu; Minxuan Han; Yongsheng Yu; Li Su (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Short-term usage of proton pump inhibitors during admission was associated with increased risk of rehospitalization in critically ill patients with myocardial infarction: a cohort study - Jia-De Zhu; Li-Juan Yang; Jian-Nan Zhao; Ping Wang; Yi-Hua Li; Xue-Sha Zhang; Jian-Mei Pan; Meng-Han Jiang; Hai-Ying Yang; Sun-Jun Yin; Gong-Hao He (European Journal of Clinical Pharmacology, 2024)

EtROP38 suppresses apoptosis of host cells infected with Eimeria tenella by inhibition of the p38MAPK pathway - Bu-ting Duan; Hao-yu Zhang; Zi-hao Song; Xiao-yi Han; Kai-ling Cui; Tong Xu; Yu Zhang; Yong-juan Zhao; Xuan Lei; Fan Tan; Lu-lu Guo; Hui-lin Yang; et al. (Veterinary Parasitology, 2024)

Associations of prenatal exposure to individual and mixed organophosphate esters with ADHD symptom trajectories in preschool children: The modifying effects of maternal Vitamin D - Han Li; Juan Tong; Xing Wang; Mengjuan Lu; Fengyu Yang; Hui Gao; Hong Gan; Shuangqin Yan; Guopeng Gao; Kun Huang; Yunxia Cao; Fangbiao Tao (Journal of Hazardous Materials, 2024)

Deciphering the effects of different types of high-temperature Daqu on the fermentation process and flavor profiles of sauce-flavor Baijiu - Wei Shi; Li-Juan Chai; Han Zhao; Ya-Ning Song; Jun-Lan Mei; Yang-Xue He; Zhen-Ming Lu; Xiao-Juan Zhang; Bo Yang; Song-Tao Wang; Cai-Hong Shen; Zheng-Hong Xu (Food Bioscience, 2024)

Phase inversion of bigels tuned by the concentration of soy protein isolate in the binary hydrogel matrix - Ling-Zhi Su; Ying-Xin Chen; Shi-Qi Zhang; Chun Hu; Jun-Bo He; Wei-Nong Zhang; Li-Juan Han (Food Hydrocolloids, 2024)

Feasibility and safety of percutaneous intramyocardial septal cryoablation: A canine model with 6-month follow-up - Xiaonan Lu; Jing Li; David H. Hsi; Juan Zhang; Yupeng Han; Shengjun Ta; Jing Wang; Jin He; Jia Zhao; Chao Han; Lu Yao; Xumei Ou; et al. (Cryobiology, 2024)

Boronate-modified electro-spun Fe doped carbon nanofibrous membrane for selective dye adsorption, catalytic degradation, and bacterial inhibition in treatment of water - De-yu Tang; Ling-ling Yan; Luo-lin Deng; Xing-han Wang; Ya-li Xiang; Qing-li Li; Juan Lin; Qing-han Zhou (Chemical Engineering Journal, 2024)

Triterpenoids from the leaves of Eleutherococcus sessiliflorus, and their antiproliferative activities in TNF-α induced HFLS-RA cells - Yan Liu; Yuqing Wang; Peng Jiang; Dong Han; Jiatong Wu; Siyi Wang; Haidan Zou; Yikai Jiang; Xiaomao Li; Juan Pan; Zhichao Hao; Wei Guan; et al. (Phytochemistry, 2024)

Long-term and efficient treatment of shale gas flowback wastewater by the novel double SEP@Fe-Mn/RGO composite membranes method - Xuehan Xiao; Zongxue Yu; Juan Wang; Shiyi Luo; Yan Huang; Dingmei Han; Junchen Li; Zhiquan Chen; Jie Wang; Minggang Huang (Desalination, 2024)

Fourteen undescribed steroidal saponins from Solanum capsicoides leaves and their neuroprotective effects - Yan Liu; Xin-Yuan Li; Jia-tong Wu; Han Wang; Xin Meng; Hai-Dan Zou; Juan Pan; Wei Guan; Adnan Mohammed Algradi; Anam Naseem; Hai-Xue Kuang; Bing-You Yang (Phytochemistry, 2024)

Overexpression of VaBAM3 from Vitis amurensis enhances seedling cold tolerance by promoting soluble sugar accumulation and reactive oxygen scavenging - Guoping Liang; Han Wang; Huimin Gou; Min Li; Yongjuan Cheng; Baozhen Zeng; Juan Mao; Baihong Chen (Plant Cell Reports, 2024)

Morphological characteristics, genetic diversity, and ethnobotanical uses of Citrus hongheensis (Rutaceae), an endangered species - Feng-Juan Mou; Jian-Qin Li; Yu-Hong Gao; Yue-Yan Li; Ting-Yao Meng; Shun-Long Han (Plant Biosystems, 2024)

Optimal N fertilizer management method for improving maize lodging resistance and yields by combining controlled-release urea and normal urea - Shiju Liu; Cangjue Pubu; Yongqi Li; Yaru Zhang; Shasha Yang; Yuanzheng Zhu; Lijin Chen; Guangxin Zhang; Juan Han (European Journal of Agronomy, 2024)

Promotional role of Ni photodepositing on Ru confined TiO2 nanotubes catalyzed CO2 methanation - Peiwei Han; Jun Zhang; Weiling Zhang; Zizhen Niu; Guowei Wang; Xiangnan Li; Juan Li; Nan Wang; Xiaoman Wang; Huangzhao Wei; Yong Chen; Xinjun Li (Chemical Engineering Journal, 2024)

Gastrodin Regulates PI3K/AKT-Sirt3 Signaling Pathway and Proinflammatory Mediators in Activated Microglia - Han-Jun Zuo; Peng-Xiang Wang; Xue-Qi Ren; Hao-Long Shi; Jin-Sha Shi; Tao Guo; Cheng Wan; Juan-Juan Li (Molecular Neurobiology, 2024)

Designing and preparing supramolecular encapsulation systems based on fraxetin and cyclodextrins for highly selective detection of nicotine - Yun-Han Yang; Zhen Zhang; Qiu-Lian Bao; Fang Zhao; Ming-Kun Yang; Xin Tao; Yan Chen; Jun-Tong Zhang; Li-Juan Yang (Carbohydrate Polymers, 2024)

Application of controlled-release urea increases maize N uptake, environmental benefits and economic returns via optimizing temporal and spatial distributions of soil mineral N - Mingxue SUN; Juan LI; Lili ZHANG; Xiaomeng SU; Ning LIU; Xiaori HAN; Songjiang WU; Zhentao SUN; Xiangdong YANG (Pedosphere, 2024)

Influence of labor migration on rural household food waste in China: Application of propensity score matching (PSM) - Guohui Shen; Xin Ru; Kunzhen Wang; Ziqi Li; Mingxue Yu; Lu Chen; Juan Han; Yanzhi Guo (Journal of Environmental Management, 2024)

α-Glucan derivatives as selective blockers of aldolase A: Computer-aided structure optimization and the effects on HCC - Qian-Han Xiao; Ze-Zhi Li; Li Ren; Shu-Yao Wang; Xiao-Qiang Li; Hong-Xin Bai; Rui-Zhi Qiao; Na Tang; Wen-Juan Liu; Jing-Mei Wang; Guang-Yuan Ma; Dian-Chao Dong; et al. (Carbohydrate Polymers, 2024)

Icariin ameliorates the cuprizone-induced demyelination associated with antioxidation and anti-inflammation - Li-Juan Song; Qing-Xian Han; Zhi-Bin Ding; Kexin Liu; Xiao-Xu Zhang; Min-Fang Guo; Dong Ma; Qing Wang; Bao-Guo Xiao; Cun-Gen Ma (Inflammopharmacology, 2024)

Insidious transmission of Mycobacterium tuberculosis in Ordos, China: a molecular epidemiology study - Hailin Sun; Zichun Ma; Fuli Ai; Bing Han; Peng Li; Juan Liu; Yiheng Wu; Yufeng Wang; Bing Li; Dan Qi; Yu Pang (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Development and evaluation of a bivalent vaccine based on recombinant newcastle disease virus expressing infectious bursal disease virus VP2L-CH3-CH4 in SPF chickens - Wen Ying Sun; Xiao Lin Cao; Yi Xuan Wang; Xiao Chen Guo; Jin Miao Liu; Zhi Qiang Xue; Hui Juan Li; Wei Wang; Ting Ting Zhang; Qianhui Li; Rui Han Qin; Yu Han Jin; et al. (Veterinary Microbiology, 2024)

Beyond fixed-speed pumped storage: A comprehensive evaluation of different flexible pumped storage technologies in energy systems - Ziwen Zhao; Meng Zhang; Mengjiao He; Yuanqiang Gao; Jianling Li; Shuo Han; Zhengguang Liu; Liuwei Lei; Juan I. Pérez Díaz; Giovanna Cavazzini; Diyi Chen (Journal of Cleaner Production, 2024)

Long-Life flexible mild Ag-Zn fibrous battery with bifunctional gel electrolyte - Yanzhe Zhu; Jiajun Fan; Shuo Zhang; Ziheng Feng; Chao Liu; Renbo Zhu; Yunjian Liu; Peiyuan Guan; Mengyao Li; Zhaojun Han; Tao Wan; Jianbo Tang; et al. (Chemical Engineering Journal, 2024)

Construction of a multiple ligation-driven exponentially symmetric T7-transcription machinery for single-molecule monitoring of diverse single-nucleotide polymorphisms in human cancers - Li-juan Wang; Xiao-wen Liu; Xinyi Zhang; Yun Han; Qian Liu; Zi-yue Wang; Chun-yang Zhang (Chemical Engineering Journal, 2024)

A comparison of milk fat globule membranes and whey proteomes: New insight into variation nutrient differences between Buffalo, Cow, Goat, and Yak - Lu Chen; Tiannuo Hong; Ziqi Li; Guohui Shen; Yanting Gu; Juan Han (Food Chemistry, 2023)

The effects of AtEXO70E2 overexpression on the secretion and production of recombinant proteins in tobacco BY-2 suspension cells - Ya Li; Juan Han; Yugu Xu; Yun Wang; Guopeng Miao (In Vitro Cellular & Developmental Biology - Plant, 2023)

Preparation and catalytic degradation of phenol achieved by utilizing pH and Upper Critical Solution Temperature dual responsive intelligent enzyme catalysts - Zhaohui Chen; Jiacong Wu; Wenrui Huang; Yuanyuan Li; Yanli Mao; Juan Han; Yun Wang; Liang Ni (Journal of Cleaner Production, 2023)

Human TRMT1 catalyzes m2G or m22G formation on tRNAs in a substrate-dependent manner - Qing-Ping Xiong; Jing Li; Hao Li; Zhi-Xuan Huang; Han Dong; En-Duo Wang; Ru-Juan Liu (Science China Life Sciences, 2023)

Complete Genome Sequence of Streptomyces sp. HP-A2021, a Promising Bacterium for Natural Product Discovery - Lan-Fang Li; Qing-Xuan Wu; Hao Wu; Yao Li; Qian Peng; Ren-Hao Han; Da-Hu Zhang; Wei-Dong Yu; Rui Xu; Juan Wang; Zhaobin Fan; Shao-Yang Hou (Biochemical Genetics, 2023)

Cost-efficient bathymetric mapping method based on massive active–passive remote sensing data - Tong Han; Huaguo Zhang; Wenting Cao; Chengfeng Le; Chen Wang; Xinke Yang; Yunhan Ma; Dongling Li; Juan Wang; Xiulin Lou (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

march2 negatively regulates antiviral immune response by targeting tbk1 in grass carp (Ctenopharyngodon idella) - Juan Du; Han Xiao; Yanqiu Hu; Zhi Li (Fish & Shellfish Immunology, 2023)

Nitidine chloride regulates cell function of bladder cancer in vitro through downregulating Lymphocyte antigen 75 - Shi-shuo Wang; Gao-qiang Zhai; Zhi-guang Huang; Jia-yuan Luo; Juan He; Jie-zhuang Huang; Ling Yang; Chu-nan Xiao; Su-li Li; Kai-rong Chen; Yan-yu Chen; Han-chu Ji; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Changes in physicochemical characteristics and metabolites in the fermentation of goji juice by Lactiplantibacillus plantarum - Han Xie; Pengyan Gao; Zhen-Ming Lu; Fang-Zhou Wang; Li-Juan Chai; Jin-Song Shi; Hui-Ling Zhang; Yan Geng; Xiao-Juan Zhang; Zheng-Hong Xu (Food Bioscience, 2023)

Immune-Ageing Evaluation of Peripheral T and NK Lymphocyte Subsets in Chinese Healthy Adults - Zhenghu Jia; Zhiyao Ren; Dongmei Ye; Jiawei Li; Yan Xu; Hui Liu; Ziyu Meng; Chengmao Yang; Xiaqi Chen; Xinru Mao; Xueli Luo; Zhe Yang; et al. (Phenomics, 2023)
Ageing is often accompanied with a decline in immune system function, resulting in immune ageing. Numerous studies have focussed on the changes in different lymphocyte subsets in diseases and immunosenescence. The change in immune phenotype is a key indication of the diseased or healthy status. However, the changes in lymphocyte number and phenotype brought about by ageing have not been comprehensively analysed. Here, we analysed T and natural killer (NK) cell subsets, the phenotype and cell differentiation states in 43,096 healthy individuals, aged 20–88 years, without known diseases. Thirty-six immune parameters were analysed and the reference ranges of these subsets were established in different age groups divided into 5-year intervals. The data were subjected to random forest machine learning for immune-ageing modelling and confirmed using the neural network analysis. Our initial analysis and machine modelling prediction showed that naïve T cells decreased with ageing, whereas central memory T cells (Tcm) and effector memory T cells (Tem) increased cluster of differentiation (CD) 28-associated T cells. This is the largest study to investigate the correlation between age and immune cell function in a Chinese population, and provides insightful differences, suggesting that healthy adults might be considerably influenced by age and sex. The age of a person's immune system might be different from their chronological age. Our immune-ageing modelling study is one of the largest studies to provide insights into ‘immune-age’ rather than ‘biological-age’. Through machine learning, we identified immune factors influencing the most through ageing and built a model for immune-ageing prediction. Our research not only reveals the impact of age on immune parameter differences within the Chinese population, but also provides new insights for monitoring and preventing some diseases in clinical practice.

The domestication-associated L1 gene encodes a eucomic acid synthase pleiotropically modulating pod pigmentation and shattering in soybean - Xiangguang Lyu; Ying-hui Li; Yanfei Li; Delin Li; Chao Han; Huilong Hong; Yu Tian; Lida Han; Bin Liu; Li-juan Qiu (Molecular Plant, 2023)

Complete biodegradation of the oldest organic herbicide 2,4-Dichlorophenoxyacetic acid by engineering Escherichia coli - Yu Wang; Yong-Sheng Tian; Jian-Jie Gao; Jing Xu; Zhen-Jun Li; Xiao-Yan Fu; Hong-Juan Han; Li-Juan Wang; Wen-Hui Zhang; Yong-Dong Deng; Cen Qian; Zhi-Hao Zuo; et al. (Journal of Hazardous Materials, 2023)

Effects of macrophytes on micro – And nanoplastic retention and cycling in constructed wetlands - Juan Huang; Rui Li; Yixuan Ma; Chong Cao; Xuan Li; Tingwei Han; Meifang Cao (Environmental Pollution, 2023)

Photoactive nano-confined Pt in titania nanotubes (Pt-TiNT) via microwave-assisted flow synthesis - Yingjian Luo; Ana Serrano-Lotina; Felicia Febriana Budihardjo; Shabnam Taghipour; Shammi Akter Ferdousi; Liping Li; Juan Jose Delgado; Ángel López-Buendía; Raquel Portela; Wei Han; Miguel A. Bañares; King Lun Yeung (Chemical Engineering Journal, 2023)

Visual detection of Staphylococcus aureus based on immunomagnetic separation and polymerase spiral reaction - Yue Zhai; Haoyan Yu; Xingxing Liu; Mengfan Zhang; Rongpeng Han; Caihong Yin; Xingchi Liu; Hui Li; Juan Li; Xiuling Song (Food Control, 2023)

Preparation, characterization and safety evaluation of Ligusticum chuanxiong essential oils liposomes for treatment of cerebral ischemia-reperfusion injury - Yu Long; Shuang Yu; Dan Li; Ai Shi; Yin Ma; Jie Deng; Xiao-qiu Li; Jing Wen; Yuan-yuan Wu; Yue Hu; Xiao-fang He; Nan Li; et al. (Food and Chemical Toxicology, 2023)

The status of the global food waste mitigation policies: experience and inspiration for China - Guohui Shen; Ziqi Li; Tiannuo Hong; Xin Ru; Kunzhen Wang; Yanting Gu; Juan Han; Yanzhi Guo (Environment, Development and Sustainability, 2023)
Food waste has become a significant challenge faced by the community with a shared future for mankind, and it has also caused a considerable impact on China's food security. Scholars across disciplines, international organizations, and especially policymakers are increasingly interested in food waste. Policies are seen as a powerful factor in reducing food waste, but current research on related policies is more scattered. This paper summarizes and analyzes the experiences of food waste policy development and implementation by systematically reviewing the studies on food waste reduction policies. The results of this paper's analysis show that current global food waste policies are focused at the national strategic level, with approaches such as legislation, food donation, waste recycling, awareness and education, and data collection. At the same time, we find that the current experience of developed countries in policy formulation and implementation is beneficial for policy formulation in developing countries. And taking China as an example, we believe that developing countries can improve food waste policies in the future by improving legislation, guiding the development of food banks, promoting social governance, and strengthening scientific research projects. These policies will all contribute strongly to global environmental friendliness. In addition, we discuss some of the factors that influence the development of food waste policies and argue that in the future, more consideration needs to be given to the effects of policy implementation and that case studies should focus more on developing countries. This will contribute to the global sustainable development process.

Indoor air particles in research vessel from Shanghai to Antarctic: Characteristics, influencing factors, and potential controlling pathway - Xudong Wu; Fange Yue; Jiancheng Wang; Xiawei Yu; Hongwei Liu; Weihua Gu; Mingming Han; Juan Li; Zhouqing Xie (Journal of Environmental Sciences, 2023)

NLRP3 Inflammasome: A key contributor to the inflammation formation - Wen-Juan Zhang; Ke-Yun Li; Yi Lan; Han-Yi Zeng; Shui-Qin Chen; Hui Wang (Food and Chemical Toxicology, 2023)

Large-scale mapping of new mixed rice cropping patterns in southern China with phenology-based algorithm and MODIS dataset - Qihui Shao; Rendong Li; Juan Qiu; Yifei Han; Dongfeng Han; MiaoMiao Chen; Hong Chi (Paddy and Water Environment, 2023)

Single bubble probe atomic force microscope and impinging-jet technique unravel the interfacial interactions controlled by long chain fatty acid in anaerobic digestion - Jian-Lu Duan; Yi Han; Li-Juan Feng; Jing-Ya Ma; Xiao-Dong Sun; Xiao-Yu Liu; Fan-Shu Geng; Jia-Li Jiang; Mei-Yan Liu; Yu-Chen Sun; Pascal Peu; Bing-Jie Ni; et al. (Water Research, 2023)

Flexible guided anti-collision device for bridge pier protection against ship collision: Numerical simulation and ship collision field test - Fei Wang; Hui-Juan Chang; Bo-Han Ma; Yong-Gang Wang; Li-Ming Yang; Jun Liu; Xin-Long Dong (Ocean Engineering, 2023)

Investigation of blueberry juice fermentation by mixed probiotic strains: Regression modeling, machine learning optimization and comparison with fermentation by single strain in the phenolic and volatile profiles - Weihua Liao; Juan Shen; Sivakumar Manickam; Sujin Li; Yang Tao; Dandan Li; Dongfeng Liu; Yongbin Han (Food Chemistry, 2023)

Crucial role of iron plaque on thallium uptake by rice plant - Xiaoyin Zhang; Wenhuan Yuan; Juan Liu; Haoran Li; Han Cai; Haiyao Hu; Dongyi Ren; Yuhua Zhang; Yuxiang Shen; Jin Wang (Waste Disposal & Sustainable Energy, 2023)
Iron plaque is a Fe-containing oxide film produced by the oxidation of Fe(II) in the rice root system under the combined action of oxygen infiltration and other microorganisms. Owing to its special surface structure and physio-chemical properties, the iron plaque has a strong absorption capacity for a variety of heavy metal ions. This study aimed to first investigate the effects of Fe species on the geochemical fractionation of Tl in typical paddy soil systems affected by industrial activities, followed by pot culture experiments to probe the effects of Fe species on the uptake and translocation of Tl in rice plants. The results of field work preliminarily showed that iron at different valences affected the conversion of the Tl geochemical fraction in the soil. Oxidizable Tl exerted significant positive correlation relationships with Fe 2+ and negative correlation relationships with Fe 3+ , while reducible Tl only displayed a positive correlation with Fe 3+ . Further analysis by pot culture experiments revealed that the contents of Fe were significantly positively correlated with Tl contents in Fe plaque ( R 2 = 0.529). In contrast, the water-soluble Tl contents in the soil were significantly negatively correlated with the contents of Fe ( R 2 = – 0. 90, p < 0.05). It suggests that the iron plaque promoted the absorption and fixation of Tl on the root surface of rice plants, causing Tl to accumulate in the iron plaque. Besides, the Tl content in the Fe plaque on the root surface of rice plants was greater than that in the above-ground tissues, which indicates that most Fe plaque exerts a certain degree of inhibition on Tl migration into the above-ground tissues of rice plants. All these findings indicate that Fe film is also an important carrier of Tl transfer in the soil–rice plant system, which provides new scientific support for the remediation of typical Tl-contaminated rice fields.

Gastrodin Regulates the Notch-1 Signal Pathway via Renin–Angiotensin System in Activated Microglia - Fang Wu; Han-Jun Zuo; Xue-Qi Ren; Peng-Xiang Wang; Fan Li; Juan-Juan Li (NeuroMolecular Medicine, 2023)

Deep learning for visual recognition and detection of aquatic animals: A review - Juan Li; Wenkai Xu; Limiao Deng; Ying Xiao; Zhongzhi Han; Haiyong Zheng (Reviews in Aquaculture, 2023)
The ocean is an important ecosystem, and aquatic animals play an important role in the biological world, especially in aquaculture. How to accurately and intelligently recognise and detect aquatic animals is one of the urgent problems in the field of underwater biological detection. The wide applications of artificial intelligence (AI), especially deep learning (DL), provide new opportunities and challenges for the efficient and intelligent exploration of aquatic animals. DL has been widely used in the visual recognition and detection of terrestrial animals, but it is in the early stages of use for aquatic animals due to the complexity of underwater environment and the difficulty of data acquisition. Here, this article reviews the current application status of DL for aquatic animals, potential challenges and future directions. The key advances of DL algorithms applied to the visual recognition and detection of aquatic animals are generalised, including datasets, algorithms and performance. The applications of DL are summarised in aquatic animals, including image detection, video detection, species classification, biomass estimation, behaviour analysis and food safety. Furthermore, the challenges are summed up and classified in the object recognition and detection domain for aquatic animals. Finally, further research direction is discussed and the conclusions are drawn. The key advances of DL in the recognition and detection of aquatic animals will help to further excavate and extend the application of DL in the field of marine biological exploration.

Soil tillage rather than crop rotation determines assembly of the wheat rhizobacterial communities - Tong Li; Huanxin Xie; Zhangheng Ren; Yuting Hou; Deqiang Zhao; Weiyan Wang; Ziting Wang; Yang Liu; Xiaoxia Wen; Juan Han; Fei Mo; Yuncheng Liao (Soil and Tillage Research, 2023)

A recyclable UCST-type biocatalyst to catalyze H2O2 degradation of phenol - Zhaohui Chen; Jiacong Wu; Wenrui Huang; Yuanyuan Li; Yanli Mao; Juan Han; Yun Wang; Liang Ni (Journal of Environmental Chemical Engineering, 2023)

Genome-wide signatures of the geographic expansion and breeding of soybean - Ying-Hui Li; Chao Qin; Li Wang; Chengzhi Jiao; Huilong Hong; Yu Tian; Yanfei Li; Guangnan Xing; Jun Wang; Yongzhe Gu; Xingpeng Gao; Delin Li; et al. (Science China Life Sciences, 2023)

Using colloidal AFM probe technique and XDLVO theory to predict the transport of nanoplastics in porous media - Li-Juan Feng; Zong-Lin Shi; Jian-Lu Duan; Yi Han; Xiao-Dong Sun; Jing-Ya Ma; Xiao-Yu Liu; Huan-Xin Zhang; Ning Guo; Chao Song; Wan-Song Zong; Xian-Zheng Yuan (Chemosphere, 2023)

Combined calcium pretreatment and ultrasonic/microwave drying to dehydrate black chokeberry: Novel mass transfer modeling and metabolic pathways of polyphenols - Rui Zhu; Juan Shen; Chung Lim Law; Xiaoxuan Ma; Dandan Li; Yongbin Han; Hossein Kiani; Sivakumar Manickam; Yang Tao (Innovative Food Science & Emerging Technologies, 2023)

The association of air pollutants with hospital outpatient visits for child and adolescence psychiatry in Shenzhen, China - Dong Fang; Wang Bing; Han Yao-hui; Jing Chun-xia; Zhang Ying; Liu Xing-li; Tian Hua-wei; Xiang Ying-jun; Liao Wan-wei; Li Xiu-juan; Fan Dong-yong; Yang Wei-ting; et al. (Environmental Research, 2023)

Local and Global Abnormalities in Pre-symptomatic Huntington’s Disease Revealed by 7T Resting-state Functional MRI - Juan-Juan Xie; Xiao-Yan Li; Yi Dong; Cong Chen; Bo-Yi Qu; Shuang Wang; Han Xu; Anna Wang Roe; Hsin-Yi Lai; Zhi-Ying Wu (Neuroscience Bulletin, 2023)

Causal gene identification and desirable trait recreation in goldfish - Peng Yu; Yang Wang; Zhi Li; Hui Jin; Liang-Liang Li; Xiao Han; Zhong-Wei Wang; Xiao-Li Yang; Xi-Yin Li; Xiao-Juan Zhang; Li Zhou; Jian-Fang Gui (Science China Life Sciences, 2022)

Associations of long-term ambient air pollution and traffic-related pollution with blood pressure and hypertension defined by the different guidelines worldwide: the CHCN-BTH study - Bingxiao Li; Han Cao; Kuo Liu; Juan Xia; Yanyan Sun; Wenjuan Peng; Yunyi Xie; Chunyue Guo; Xiaohui Liu; Fuyuan Wen; Fengxu Zhang; Guangliang Shan; et al. (Environmental Science and Pollution Research, 2022)

Multi-watershed nonpoint source pollution management through coupling Bayesian-based simulation and mechanism-based effluent trading optimization - Xiaomei Xu; Xueting Zeng; Yongping Li; Chunrong Wang; Lei Yu; Guohe Huang; Junlong Zhang; Juan Feng; Xinyu Han (Stochastic Environmental Research and Risk Assessment, 2022)

Development and structure of four different stamens in Clematis macropetala (Ranunculaceae): particular emphasis on staminodes and staminal nectary - Wen-juan Li; Zi-xuan Huang; Meng Han; Yi Ren; Xiao-hui Zhang (Protoplasma, 2022)

Latitudinal patterns of climatic variables and influence of local topography on climatic variables in the dry valleys of southwestern China - Xiao-juan Li; Xin Liu; Han-yue Zhang; Wei-kai Bao (Journal of Mountain Science, 2022)

Analyses of Botrytis cinerea-responsive LrWRKY genes from Lilium regale reveal distinct roles of two LrWRKY transcription factors in mediating responses to B. cinerea - Yongyao Fu; Juan Li; Han Wu; Sijia Jiang; Yiyong Zhu; Chunyu Liu; WenJi Xu; Qiang Li; Liping Yang (Plant Cell Reports, 2022)

Developing a highly efficient regeneration system for leaves of tissue-cultured tetraploid Robinia pseudoacacia L. - Xiuyu Li; Qi Guo; Chao Han; Juan Li; Li Dong; Sen Cao; Zijie Zhang; Yuhan Sun; Ruohan Wang; Yun Li (In Vitro Cellular & Developmental Biology - Plant, 2022)

Microbacterium sulfonylureivorans sp. nov., isolated from sulfonylurea herbicides degrading consortium - Qingyun Ma; Delong Kong; Qi Zhang; Miaomiao Li; Xiaoyan Han; Juan Che; Yiqing Zhou; Wei Zhang; Xu Jiang; Zhiyong Ruan (Archives of Microbiology, 2022)

Distinct durability of IgM/IgG antibody responses in COVID-19 patients with differing severity - Junyan Han; Ning Zhang; Danying Chen; Yuhuan Gong; Guoli Li; Yaxian Kong; Lin Pu; Chen Chen; Jingyuan Liu; Qi Wang; Ju Zhang; Xuesen Zhao; et al. (Science China Life Sciences, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

The influence of Stokes drift on oil spills: Sanchi oil spill case - Yiqiu Yang; Yan Li; Juan Li; Jingui Liu; Zhiyi Gao; Kaixuan Guo; Han Yu (Acta Oceanologica Sinica, 2021)

Interaction between the cell walls of microalgal host and fungal carbohydrate‐activate enzymes is essential for the pathogenic parasitism process - Juan Lin; Hailong Yan; Liang Zhao; Yanhua Li; Bahareh Nahidian; Mianmian Zhu; Qiang Hu; Danxiang Han (Environmental Microbiology, 2021)
Summary Fungi can parasitize microalgae, exerting profound impacts on both the aquatic ecosystems and microalgal mass cultures. In this study, the unicellular green alga Haematococcus pluvialis and the blastocladialean fungus Paraphysoderma sedebokerense were used as a model system to address the mechanisms underlying the fungal parasitism on the algal host. High‐throughput metabolic assay indicated that P . sedebokerense can utilize several carbon sources with a preference for mannose, glucose and their oligosaccharides, which was compatible with the profile of the host algal cell walls enriched with glucan and mannan. The results of dual transcriptomics analysis suggested that P . sedebokerense can upregulate a large number of putative carbohydrate‐activate enzymes (CAZymes) encoding genes, including those coding for the endo‐1,4‐β‐glucanase and endo‐1,4‐β‐mannanase during the infection process. The cell walls of H . pluvialis can be decomposed by both P . sedebokerense and commercial CAZymes (e.g. cellulase and endo‐1,4‐β‐mannanase) to produce mannooligomers, while several putative parasitism‐related genes of P . sedebokerense can be in turn upregulated by mannooligomers. In addition, the parasitism can be blocked by interfering the selected CAZymes including glucanase, mannanase and lysozyme with the specific inhibitors, which provided a framework for screening suitable compounds for pathogen mitigation in algal mass culture.

Genomic selection to introgress exotic maize germplasm into elite maize in China to improve kernel dehydration rate - Hongjun Yong; Nan Wang; Xiaojun Yang; Fengyi Zhang; Juan Tang; Zhiyuan Yang; Xinzhe Zhao; Yi Li; Mingshun Li; Degui Zhang; Zhuanfang Hao; Jianfeng Weng; et al. (Euphytica, 2021)

Different posterior hippocampus and default mode network modulation in young APOE ε4 carriers: a functional connectome-informed phenotype longitudinal study - Li Juan Zheng; Li Lin; U. Joseph Schoepf; Akos Varga-Szemes; Rock H. Savage; Han Zhang; Yun Fei Wang; Xin Yuan Zhang; Song Luo; Ya Liu; Gui Fen Yang; Guang Ming Lu; et al. (Molecular Neurobiology, 2021)

Shattering-resistance of an elite soybean variety ‘Heihe 43’ and identification of shattering-resistant genes - Dezhi Han; Jianan Han; Siqi Jiang; Bohong Su; Bo Zhang; Zhangxiong Liu; Hongrui Yan; Li-Juan Qiu (Euphytica, 2021)

Puerhibacterium puerhi gen. nov., sp. nov., a novel member of the family Promicromonosporaceae, isolated from Pu-erh tea pile-fermentation - Rui-Juan Yang; De Zhou; Qiao-Mei Wang; Lu Han; Wen-Shu Peng; Li Liu; Xuan-Jun Wang; Liang Yan; Jie Lv; Jun Sheng (Archives of Microbiology, 2021)

Tweety-Homolog 1 Facilitates Pain via Enhancement of Nociceptor Excitability and Spinal Synaptic Transmission - Wen-Juan Han; Sui-Bin Ma; Wen-Bin Wu; Fu-Dong Wang; Xiu-Li Cao; Dong-Hao Wang; Hai-Ning Wu; Rou-Gang Xie; Zhen-Zhen Li; Fei Wang; Sheng-Xi Wu; Min-Hua Zheng; et al. (Neuroscience Bulletin, 2021)

The Fe3O4-modified biochar reduces arsenic availability in soil and arsenic accumulation in indica rice (Oryza sativa L.) - Yao Yao; Hang Zhou; Xiu-Lan Yan; Xiao Yang; Kang-Wen Huang; Juan Liu; Li-Juan Li; Jing-Yi Zhang; Jiao-Feng Gu; Yaoyu Zhou; Bo-Han Liao (Environmental Science and Pollution Research, 2021)

Impacts of native vegetation on the hydraulic properties of the concentrated flows in bank gullies - Zheng-an Su; Zhou-yao He; Tao Zhou; Jun-jie Wang; Xiao-yi Wang; Li-juan Wang; Hai-dong Fang; Liang-tao Shi; Yi-han Liu; Zuo Wu (Journal of Mountain Science, 2021)

EmhR is an indole‐sensing transcriptional regulator responsible for the indole‐induced antibiotic tolerance in Pseudomonas fluorescens - Jian‐Ting Han; Di‐Yin Li; Meng‐Yuan Zhang; Xiao‐Quan Yu; Xiang‐Xue Jia; Hang Xu; Xu Yan; Wen‐Juan Jia; Shaomin Niu; Megan L. Kempher; Xuanyu Tao; Yong‐Xing He (Environmental Microbiology, 2021)
Summary Indole is well known as an interspecies signalling molecule to modulate bacterial physiology; however, it is not clear how the indole signal is perceived and responded to by plant growth promoting rhizobacteria (PGPR) in the rhizosphere. Here, we demonstrated that indole enhanced the antibiotic tolerance of Pseudomonas fluorescens 2P24, a PGPR well known for its biocontrol capacity. Proteomic analysis revealed that indole influenced the expression of multiple genes including the emhABC operon encoding a major multidrug efflux pump. The expression of emhABC was regulated by a TetR‐family transcription factor EmhR, which was demonstrated to be an indole‐responsive regulator. Molecular dynamics simulation showed that indole allosterically affected the distance between the two DNA‐recognizing helices within the EmhR dimer, leading to diminished EmhR–DNA interaction. It was further revealed the EmhR ortholog in Pseudomonas syringae was also responsible for indole‐induced antibiotic tolerance, suggesting this EmhR‐dependent, indole‐induced antibiotic tolerance is likely to be conserved among Pseudomonas species. Taken together, our results elucidated the molecular mechanism of indole‐induced antibiotic tolerance in Pseudomonas species and had important implications on how rhizobacteria sense and respond to indole in the rhizosphere.

Effects of degradation succession of alpine wetland on soil organic carbon and total nitrogen in the Yellow River source zone, west China - Chun-ying Lin; Xi-lai Li; Jing Zhang; Hua-fang Sun; Juan Zhang; Hui-bang Han; Qi-hua Wang; Cheng-biao Ma; Cheng-yi Li; Yu-xing Zhang; Xue-qian Ma (Journal of Mountain Science, 2021)

Spatial variation in macrobenthic assemblages and their relationship with environmental factors in the upstream and midstream regions of the Heihe River Basin, China - Yu Wang; Juan-Juan Liu; Wei Liu; Qi Feng; Bao-long Li; Han Lu; Shuang Wang (Environmental Monitoring and Assessment, 2021)
The Heihe River is a typical inland river under increasing anthropogenic pressure. To explore the characteristics of the macrobenthic assemblages and their relationships with environmental factors in the upstream and midstream regions of this basin, abiotic conditions and macrobenthic assemblages were investigated in the summers of 2018 and 2019. A total of 50 species were collected, and Arthropoda and mollusks were the dominant groups. A significant increase in standing stock was observed from the upstream to midstream, and predators (PR) were the main functional feeding group. A one-way analysis of variance (ANOVA) revealed that the Shannon-Wiener index and Margalef’s index values significantly differed at the spatial scale ( P < 0.05). A redundancy analysis (RDA) and Pearson correlation analysis showed that the spatial heterogeneity of the macrobenthos was influenced by the biochemical oxygen demand (BOD 5 ), water temperature (WT), total nitrogen (TN), salinity, electrical conductivity (EC), total dissolved solids (TDS), dissolved oxygen (DO), and potassium permanganate index (COD Mn ) ( P < 0.05). The spatial variation of macrobenthos was mainly governed by natural conditions and human disturbances.

Partial recovery of disturbed V-J pairing profiles of T-cell receptor in people living with HIV receiving long-term antiretroviral therapy - Guoli Li; Jiarui Li; Henghui Zhang; Yu Zhang; Di Liu; Yu Hao; Junyan Han; Juan Du; Liuluan Zhu; Yongqin Zeng; Bei Li; Rui Li; et al. (Science China Life Sciences, 2021)

Gut dysbiosis-influence on amygdala-based functional activity in patients with end stage renal disease: a preliminary study - Li Juan Zheng; Li Lin; Jianhui Zhong; Zhihong Zhang; Yu Bing Ye; Xin Yuan Zhang; Yun Fei Wang; Han Zhang; Ya Liu; Guang Ming Lu; Dehua Gong; Long Jiang Zhang (Brain Imaging and Behavior, 2020)

Characteristics of chemotherapy-induced diabetes mellitus in acute lymphoblastic leukemia patients - Shan-shan Suo; Chen-ying Li; Yi Zhang; Jing-han Wang; Yin-jun Lou; Wen-juan Yu; Jie Jin (Journal of Zhejiang University-SCIENCE B, 2020)

Two types of hyperthermal events in the Mesozoic-Cenozoic: Environmental impacts, biotic effects, and driving mechanisms - Xiumian Hu; Juan Li; Zhong Han; Yongxiang Li (Science China Earth Sciences, 2020)

Decadal change in summer precipitation over the east of Northwest China and its associations with atmospheric circulations and sea surface temperatures - Shasha Shang; Gaofeng Zhu; Ruolin Li; Jie Xu; Juan Gu; Huiling Chen; Xiaowen Liu; Tuo Han (International Journal of Climatology, 2020)
As global warming has progressed, precipitation patterns over arid Northwest China have undergone significant change. In this study, changes in summer (JJA) precipitation over the eastern part of Northwest China (ENWC) from 1980 to 2014 were investigated using the China gridded monthly precipitation dataset (CN05.1). The results showed that summer precipitation over the ENWC experienced a decadal wet‐to‐dry shift in 1998. Westerlies played an important role in the upper atmospheric levels in terms of water vapour transport; the decadal variations in summer precipitation were principally controlled by the water vapour input from the ENWC's western boundary. In addition, the decadal variations in summer precipitation in the ENWC appear to be associated with a meridional teleconnection around 110°E and a zonal pattern over 45–60°N in the lower troposphere. These two teleconnections led to cyclonic anomalies in the ENWC and enhanced water vapour transport into the ENWC, resulting in above‐normal precipitation during the 1989–1998 decadal period. Further, the warmer (colder) sea surface temperatures (SSTs) observed in the tropical Eastern Pacific correspond to the southward (northward) displacement of the Asian jet stream and a negative (positive) phase of the Silk Road pattern, resulting in a wet (dry) ENWC. Moreover, the SST anomalies in the North Atlantic and Northwest Pacific may affect summer precipitation over the ENWC via a zonal teleconnection in the middle troposphere.

Scutellarin Exerts Anti-Inflammatory Effects in Activated Microglia/Brain Macrophage in Cerebral Ischemia and in Activated BV-2 Microglia Through Regulation of MAPKs Signaling Pathway - Hao-Lun Chen; Wen-Ji Jia; Hong-E Li; Hong Han; Fan Li; Xiao-Li-Na Zhang; Juan-Juan Li; Yun Yuan; Chun-Yun Wu (NeuroMolecular Medicine, 2020)

Effect of five modified mass selection cycles on combining ability in two Chinese maize populations - Hongjun Yong; Juan Tang; Xinzhe Zhao; Fengyi Zhang; Zhiyuan Yang; Yi Li; Mingshun Li; Degui Zhang; Zhuanfang Hao; Jianfeng Weng; Jienan Han; Bo Peng; et al. (Euphytica, 2020)

Viral metagenomics reveals sapoviruses of different genogroups in stool samples from children with acute gastroenteritis in Jiangsu, China - Wang Li; Surong Dong; Juan Xu; Xiaobin Zhou; Junling Han; Zhaqing Xie; Qin Gong; Hailin Peng; Chenglin Zhou; Mei Lin (Archives of Virology, 2020)
Sapoviruses (SAVs), including several genogroups (GI to GV), are one of the causes of acute gastroenteritis (AGE). In this study, viral metagenomics revealed the presence of sapoviruses of different genogroups in stool from children with AGE. Eight different complete SAV genomes were determined, of which five belonged to GI and the other three belonged to GII, GIV and GV, respectively. Although they were highly similar to published sequences, the GIV and GV were the first complete genome sequences of these SAVs found in China. In a prevalence investigation, 19% of subjects with AGE were positive for SAVs, while none of the control group was positive.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Review of Chinese atmospheric science research over the past 70 years: Synoptic meteorology - Zhiyong Meng; Fuqing Zhang; Dehai Luo; Zhemin Tan; Juan Fang; Jianhua Sun; Xueshun Shen; Yunji Zhang; Shuguang Wang; Wei Han; Kun Zhao; Lei Zhu; et al. (Science China Earth Sciences, 2019)

The Rho kinase inhibitor fasudil attenuates Aβ1–42-induced apoptosis via the ASK1/JNK signal pathway in primary cultures of hippocampal neurons - Ye Gao; Yuqing Yan; Qingli Fang; Nianping Zhang; Gajendra Kumar; Jihong Zhang; Li-Juan Song; Jiezhong Yu; Linhu Zhao; Han-Ting Zhang; Cun-Gen Ma (Metabolic Brain Disease, 2019)

Angiotensin II induces apoptosis of cardiac microvascular endothelial cells via regulating PTP1B/PI3K/Akt pathway - Yanyan Wang; Yuyuan Fan; Yu Song; Xueting Han; Mingqiang Fu; Jingfeng Wang; Xiaotong Cui; Juan Cao; Li Chen; Kai Hu; Aijun Sun; Jingmin Zhou; et al. (In Vitro Cellular & Developmental Biology - Animal, 2019)

Quantifying Flood Frequency Modification Caused by Multi-Reservoir Regulation - Yi-han Tang; Jie-feng Wu; Pei-yi Li; Li-juan Zhang; Xiao-hong Chen; Kai-rong Lin (Water Resources Management, 2019)

Association of Genetic Polymorphisms with Age at Onset in Han Chinese Patients with Bipolar Disorder - Shao-Hua Hu; Yu-Qing Han; Ting-Ting Mou; Man-Li Huang; Jian-Bo Lai; Chee H Ng; Jing Lu; Qiao-Qiao Lu; Qiu-Yan Lin; Yu-Zhi Zhang; Jian-Bo Hu; Ning Wei; et al. (Neuroscience Bulletin, 2019)

Growth, artificial seedling raising and cultivation of Sargassum confusum (Fucales, Phaeophyceae) inhabiting the coast of Shandong Peninsula, China - Jinhua Pan; Zhuangzhi Zhang; Shenhui Yu; Houwei Han; Xin Jiang; Liming Jiang; Guangjin Liang; Juan Sun; Xiaojie Li; Guanpin Yang (Journal of Applied Phycology, 2019)

Greenhouse gas mitigation potential of balanced fertilization cropland under double-cropping systems: a case study in Shaanxi province, China - Changjiang Li; Changzhen Li; Juan Han; Junli Zhang; Yangfeng Wang; Fei Yang; Xiaoxia Wen; Yuncheng Liao (Environmental Monitoring and Assessment, 2019)

Transcription profiles reveal the regulatory mechanisms of spur bud changes and flower induction in response to shoot bending in apple (Malus domestica Borkh.) - Libo Xing; Dong Zhang; Siyan Qi; Xilong Chen; Na An; Youmei Li; Caiping Zhao; Mingyu Han; Juan Zhao (Plant Molecular Biology, 2019)

Structure and fracture-cavity identification of epimetamorphic volcanic-sedimentary rock basement reservoir: a case study from central Hailar Basin, China - Juan Li; Guangpo Chen; Bin Zhang; Liang Hong; Qianfeng Han (Arabian Journal of Geosciences, 2019)

Genesis of the Angeer Yinwula Pb–Zn deposit, Inner Mongolia, China: constraints from fluid inclusions, C–H–O–S–Pb isotope systematics, and zircon U–Pb geochronology - Han-Lun Liu; Yi Han; Ke-Yong Wang; Wen Li; Jian Li; Wen-Yan Cai; Li-Juan Fu (Arabian Journal of Geosciences, 2018)

Investigation of microorganisms involved in kefir biofilm formation - Xue Han; Li-Juan Zhang; Hui-Ying Wu; Yi-Fan Wu; Sai-Nan Zhao (Antonie van Leeuwenhoek, 2018)

A new12-membered lactone from the stems of Ficus auriculata - Tai-Ming Shao; Cai-Juan Zheng; Xiao-Bao Li; Guang-Ying Chen; Xiao-Ping Song; Chang-Ri Han (Natural Product Research, 2018)

Histamine Excites Striatal Dopamine D1 and D2 Receptor-Expressing Neurons via Postsynaptic H1 and H2 Receptors - Qian-Xing Zhuang; Han-Ting Xu; Xu-Juan Lu; Bin Li; Wing-Ho Yung; Jian-Jun Wang; Jing-Ning Zhu (Molecular Neurobiology, 2018)

SNAI1, an endothelial–mesenchymal transition transcription factor, promotes the early phase of ocular neovascularization - Jia-Xing Sun; Tian-Fang Chang; Man-Hong Li; Li-Juan Sun; Xian-Chun Yan; Zi-Yan Yang; Yuan Liu; Wen-Qin Xu; Yang Lv; Jing-Bo Su; Liang Liang; Hua Han; et al. (Angiogenesis, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Species-based classification reveals spatial processes of phytoplankton meta-communities better than functional group approaches: a case study from three freshwater lake regions in China - Li-Juan Xiao; Yiqiu Zhu; Yang Yang; Qiuqi Lin; Bo-Ping Han; Judit Padisák (Hydrobiologia, 2018)

Complete nucleotide sequence of jasmine virus H, a new member of the family Tombusviridae - Tao Zhuo; Li-Juan Zhu; Cheng-Cong Lu; Chao-Yang Jiang; Zi-Yin Chen; Guangzhi Zhang; Zong-Hua Wang; Juan Jovel; Yan-Hong Han (Archives of Virology, 2018)

Sex-specific competition differently regulates ecophysiological responses and phytoremediation of Populus cathayana under Pb stress - Juan Chen; Qingquan Han; Baoli Duan; Helena Korpelainen; Chunyang Li (Plant and Soil, 2017)

A new biphenyl derivative from the mangrove endophytic fungus Phomopsis longicolla HL-2232 - Xiao-Bao Li; Guang-Ying Chen; Rui-Jie Liu; Cai-Juan Zheng; Xin-Ming Song; Chang-Ri Han (Natural Product Research, 2017)

Optimum ridge-to-furrow ratio in ridge-furrow mulching systems for improving water conservation in maize (Zea may L.) production - Weiwei Li; Xiaoxia Wen; Juan Han; Yang Liu; Wei Wu; Yuncheng Liao (Environmental Science and Pollution Research, 2017)

One new lignan derivative from the Combretum alfredii Hance - Meng Bai; Li-Jun Wu; Yue Cai; Shou-Yuan Wu; Xiao-Ping Song; Guang-Ying Chen; Cai-Juan Zheng; Chang-Ri Han (Natural Product Research, 2017)

Cryopreservation of Jerusalem artichoke cultivars using an improved droplet-vitrification method - Jin-Mei Zhang; Li Han; Xin-Xiong Lu; Gayle M. Volk; Xia Xin; Guang-Kun Yin; Juan-Juan He; Ling Wang; Xiao-Ling Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2017)

Responses of Dissimilatory Nitrate Reduction to Ammonium and Denitrification to Plant Presence, Plant Species and Species Richness in Simulated Vertical Flow Constructed Wetlands - Chong-Bang Zhang; Wen-Li Liu; Wen-Juan Han; Ming Guan; Jiang Wang; Shu-Yuan Liu; Ying Ge; Jie Chang (Wetlands, 2017)

Insulin-independent GLUT4 translocation in proliferative vascular smooth muscle cells involves SM22α - Li-Li Zhao; Fan Zhang; Peng Chen; Xiao-Li Xie; Yong-Qing Dou; Yan-Ling Lin; Lei Nie; Pin Lv; Dan-Dan Zhang; Xiao-Kun Li; Sui-Bing Miao; Ya-Juan Yin; et al. (Journal of Molecular Medicine, 2017)

Histochemical examination of systemic administration of eldecalcitol combined with guided bone regeneration for bone defect restoration in rats - Xiuchun Han; Juan Du; Di Liu; Hongrui Liu; Norio Amizuka; Minqi Li (Journal of Molecular Histology, 2017)

Improved salt tolerance of medicinal plant Codonopsis pilosula by Bacillus amyloliquefaciens GB03 - Qing-Qing Han; Yong-Na Wu; Hui-Juan Gao; Rui Xu; Paul W. Paré; Huazhong Shi; Qi Zhao; Hui-Ru Li; Sardar Ali Khan; Yin-Quan Wang; Suo-Min Wang; Jin-Lin Zhang (Acta Physiologiae Plantarum, 2017)

Citricoccus lacusdiani sp. nov., an actinobacterium promoting Microcystis growth with limited soluble phosphorus - Bing-Huo Zhang; Nimaichand Salam; Juan Cheng; Min Xiao; Han-Quan Li; Jian-Yuan Yang; Dai-Ming Zha; Wen-Jun Li (Antonie van Leeuwenhoek, 2016)

One new berberine from the branches and leaves of Polyalthia obliqua Hook.f. & Thomson - Li-Jun Wu; Cai-Juan Zheng; Liu-Kai Wang; Chang-Ri Han; Xiao-Ping Song; Guang-Ying Chen; Xue-ming Zhou; Shou-yuan Wu; Xiao-bao Li; Meng Bai; Chun-xin Liu; Jun Yao (Natural Product Research, 2016)

Expression quantitative trait loci in long non-coding RNA PAX8-AS1 are associated with decreased risk of cervical cancer - Jing Han; Wen Zhou; Meiqun Jia; Juan Wen; Jie Jiang; Jufang Shi; Kai Zhang; Hongxia Ma; Jibin Liu; Jiansong Ren; Min Dai; Zhibin Hu; et al. (Molecular Genetics and Genomics, 2016)

Histochemical examination of the effects of high-dose 1,25(OH)2D3 on bone remodeling in young growing rats - Jing Sun; Bao Sun; Wei Wang; Xiuchun Han; Hongrui Liu; Juan Du; Wei Feng; Bo Liu; Norio Amizuka; Minqi Li (Journal of Molecular Histology, 2016)

Increased telocytes involved in the proliferation of vascular smooth muscle cells in rat carotid artery balloon injury - Yanyan Li; Xiuxiu Zhang; Juan Gao; Han Xiao; Ming Xu (Science China Life Sciences, 2016)

Combinatorial enzymatic digestion with thermolysin and collagenase type I improved the isolation and culture effects of hair cell progenitors from rat cochleae - Yong-li Song; Ke-yong Tian; Wen-juan Mi; Peng Han; Zhong-jia Ding; Yang Qiu; Fu-quan Chen; Jian-jua Qiu (In Vitro Cellular & Developmental Biology - Animal, 2016)

The effect of calcitriol on high mobility group box 1 expression in periodontal ligament cells during orthodontic tooth movement in rats - Jian Cui; Juan Li; Wei Wang; Xiuchun Han; Juan Du; Jing Sun; Wei Feng; Bo Liu; Hongrui Liu; Norio Amizuka; Minqi Li (Journal of Molecular Histology, 2016)

PI3K/Akt/FoxO3a signaling mediates cardioprotection of FGF-2 against hydrogen peroxide-induced apoptosis in H9c2 cells - Mi-Hua Liu; Guo-Hua Li; Li-Jun Peng; Shun-Lin Qu; Yuan Zhang; Juan Peng; Xin-Yuan Luo; Heng-Jing Hu; Zhong Ren; Yao Liu; Hui Tang; Lu-Shan Liu; et al. (Molecular and Cellular Biochemistry, 2016)

Boosting BCG-primed mice with chimeric DNA vaccine HG856A induces potent multifunctional T cell responses and enhanced protection against Mycobacterium tuberculosis - Ping Ji; Zhi-Dong Hu; Han Kang; Qin Yuan; Hui Ma; Han-li Wen; Juan Wu; Zhong-Ming Li; Douglas B. Lowrie; Xiao-Yong Fan (Immunologic Research, 2016)

Dissimilarity of phytoplankton assemblages in two connected tropical reservoirs: effects of water transportation and environmental filtering - Li-Juan Xiao; Ren Hu; Liang Peng; La-Mei Lei; Yu Feng; Bo-Ping Han (Hydrobiologia, 2016)

Enteractinococcus lamae sp. nov. and Enteractinococcus viverrae sp. nov., isolated from animal faeces - Xiu Chen; Gui-Ding Li; Qin-Yuan Li; Cai-Juan Hu; Shu-Mei Qiu; Yi Jiang; Cheng-Lin Jiang; Li Han; Xue-Shi Huang (Antonie van Leeuwenhoek, 2015)

Effects of light intensity on the susceptibility of Nicotiana tabacum to cucumber mosaic virus - Li-Juan Chen; Han Ren; Xing-Guang Deng; Ya-Nan Li; Wen-Qiong Cha; Hong-Hui Lin; De-Hui Xi (Journal of General Plant Pathology, 2015)

Histochemical evidence of zoledronate inhibiting c-src expression and interfering with CD44/OPN-mediated osteoclast adhesion in the tibiae of mice - Hongrui Liu; Jian Cui; Jing Sun; Juan Du; Wei Feng; Bao Sun; Juan Li; Xiuchun Han; Bo Liu; Yimin; Kimimitsu Oda; Norio Amizuka; et al. (Journal of Molecular Histology, 2015)

Altered distribution of HMGB1 in the periodontal ligament of periostin-deficient mice subjected to Waldo’s orthodontic tooth movement - Juan Li; Wei Feng; Bo Liu; Bao Sun; Xiuchun Han; Juan Du; Jing Sun; Yimin; Jian Cui; Jie Guo; Akira Kudo; Norio Amizuka; et al. (Journal of Molecular Histology, 2015)

Smooth muscle 22α facilitates angiotensin II-induced signaling and vascular contraction - Xiao-Li Xie; Xi Nie; Jun Wu; Fan Zhang; Li-Li Zhao; Yan-Ling Lin; Ya-Juan Yin; Hui Liu; Ya-Nan Shu; Sui-Bing Miao; Huan Li; Peng Chen; et al. (Journal of Molecular Medicine, 2015)

Retrospective Review on Obstetric Cases of Critically Ill and Dead Patients in Dongguan - Li-Han Shen; Yun-Yong Fang; Yan-Bing Zheng; Li-Juan Xiao; Su-Ran Huang; Xi-Zhen Liu; Li-Hua Cai (Cell Biochemistry and Biophysics, 2015)

Expression of HMGB1 in the periodontal tissue subjected to orthodontic force application by Waldo’s method in mice - Shengyu Lv; Juan Li; Wei Feng; Hongrui Liu; Juan Du; Jing Sun; Jian Cui; Bao Sun; Xiuchun Han; Kimimitsu Oda; Norio Amizuka; Xin Xu; et al. (Journal of Molecular Histology, 2015)

In vitro and in vivo protection against enterovirus 71 by an antisense phosphorothioate oligonucleotide - Juan Liu; Zhe Zhou; Kang Li; Mingming Han; Jing Yang; Shengqi Wang (Archives of Virology, 2014)

The toxicity of cerium nitrate to Elodea canadensis: subcellular distribution, chemical forms and physiological effects - Wei Yue Chu; San Juan Cai; Yong Yang Fu; Fei Fei Li; Ting Xu; Han Qiu; Qin Song Xu (Acta Physiologiae Plantarum, 2014)

Vanillin derivatives as the selective small molecule inhibitors of FtsZ - Juan Sun; Ming-Hui Li; Xin-Yi Wang; Yang Zhang; Rong-Ju Yuan; Han-Yu Liu; Hai-Liang Zhu (Medicinal Chemistry Research, 2014)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Differences in Gene Expression and Regulation during Ontogenetic Phase Change in Apple Seedlings - Yan Gao; Feng Qiu Yang; Xin Cao; Chun Min Li; Yi Wang; Yong Bo Zhao; Guang Juan Zeng; Dong Mei Chen; Zhen Hai Han; Xin Zhong Zhang (Plant Molecular Biology Reporter, 2014)

Infection of Prions and Treatment of PrP106–126 Alter the Endogenous Status of Protein 14-3-3 and Trigger the Mitochondrial Apoptosis Possibly via Activating Bax Pathway - Qi Shi; Qin-Qin Song; Peng Sun; Jin Zhang; Juan Song; Li-Na Chen; Kang Xiao; Shao-Bin Wang; Ya-Zhou Zhang; Gong-Qi Li; Lin-Jun Sheng; Bao-Dong Wang; et al. (Molecular Neurobiology, 2014)

Streptomyces jiujiangensis sp. nov., isolated from soil in South China - Bing-Huo Zhang; Juan Cheng; Li Li; Yong-Guang Zhang; Hong-Fei Wang; Han-Quan Li; Jian-Yuan Yang; Wen-Jun Li (Antonie van Leeuwenhoek, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

β-Ionone arrests cell cycle of gastric carcinoma cancer cells by a MAPK pathway - Hong-Wei Dong; Shuang Zhang; Wen-Guang Sun; Qian Liu; Juan C. Ibla; Sulpicio G. Soriano; Xiao-Hui Han; Lian-Xin Liu; Ming-Song Li; Jia-Ren Liu (Archives of Toxicology, 2013)

Lack of association between IL-23R gene polymorphisms and systemic lupus erythematosus in a Chinese population - Gui-Mei Chen; Chen-Chen Feng; Qian-Ling Ye; Juan Wang; Han Cen; Rui Li; Hui Peng; Mo Zhou; Rui-Xue Leng; Yin-Guang Fan; Jin-Hui Tao; Hai-Feng Pan; et al. (Inflammation Research, 2013)

Apoptosis initiation of β-ionone in SGC-7901 gastric carcinoma cancer cells via a PI3K-AKT pathway - Qian Liu; Hong-Wei Dong; Wen-Guang Sun; Ming Liu; Juan C. Ibla; Lian-Xin Liu; John W. Parry; Xiao-Hui Han; Ming-Song Li; Jia-Ren Liu (Archives of Toxicology, 2013)

SOD1 gene transfer into paraventricular nucleus attenuates hypertension and sympathetic activity in spontaneously hypertensive rats - Ning Yuan; Feng Zhang; Ling-Li Zhang; Juan Gao; Ye-Bo Zhou; Ying Han; Guo-Qing Zhu (Pflügers Archiv - European Journal of Physiology, 2013)

Formation of soluble microbial products (SMP) by activated sludge at various salinities - Yan Li; Ai-Min Li; Juan Xu; Wen-Wei Li; Han-Qing Yu (Biodegradation, 2013)

Analysis of the genetic effects of prolactin gene polymorphisms on chicken egg production - Hui-Fang Li; Jing-Ting Shu; Yu-Feng Du; Yan-Ju Shan; Kuan-Wei Chen; Xue-Yu Zhang; Wei Han; Wen-Juan Xu (Molecular Biology Reports, 2013)

Association between mandibular posterior alveolar morphology and growth pattern in a Chinese population with normal occlusion - Min Han; Rong-yang Wang; Hong Liu; Xiu-juan Zhu; Fu-lan Wei; Tao Lv; Na-na Wang; Li-hua Hu; Guo-ju Li; Dong-xu Liu; Chun-ling Wang (Journal of Zhejiang University-SCIENCE B, 2013)

NADPH oxidase 2 plays a critical role in dysfunction and apoptosis of pancreatic β-cells induced by very low-density lipoprotein - Juan Jiao; Lin Dou; Miao Li; Yonggang Lu; Han-Bang Guo; Yong Man; Shu Wang; Jian Li (Molecular and Cellular Biochemistry, 2012)

Should few retrieved oocytes be as an indication for intracytoplasmic sperm injection? - Qing-song Xi; Li-xia Zhu; Juan Hu; Li Wu; Han-wang Zhang (Journal of Zhejiang University-SCIENCE B, 2012)

Biofilm formation and microbial community analysis of the simulated river bioreactor for contaminated source water remediation - Xiang-Yang Xu; Li-Juan Feng; Liang Zhu; Jing Xu; Wei Ding; Han-Ying Qi (Environmental Science and Pollution Research, 2012)

Simvastatin has beneficial effect on pulmonary artery hypertension by inhibiting NF-κB expression - Zhong-qiang Liu; Bing Liu; Li Yu; Xiao-qing Wang; Juan Wang; Han-min Liu (Molecular and Cellular Biochemistry, 2011)

Determination of optimal carbon source and pH value for sclerotial formation of Polyporus umbellatus under artificial conditions - Yong-Mei Xing; Juan Chen; Ya-Li Lv; Han-Qiao Liang; Shun-Xing Guo (Mycological Progress, 2011)

A Novel Cytoplasmic Isopentenyl Diphosphate Isomerase Gene from Tomato (Solanum lycopersicum): Cloning, Expression, and Color Complementation - Jin Sun; Yu-Yang Zhang; Hui Liu; Zhe Zou; Chan-Juan Zhang; Xiao-Hui Zhang; Han-Xia Li; Zhi-Biao Ye (Plant Molecular Biology Reporter, 2010)

Molecular Characterisation of the Faecal Microbiota in Patients with Type II Diabetes - Xiaokang Wu; Chaofeng Ma; Lei Han; Muhammad Nawaz; Fei Gao; Xuyan Zhang; Pengbo Yu; Chang’an Zhao; Lianchuan Li; Aiping Zhou; Juan Wang; John E. Moore; et al. (Current Microbiology, 2010)

Inhibition of human lung adenocarcinoma growth using survivint34a by low-dose systematic administration - Yan Shan; Chunting Wang; Li Yang; Li Juan Chen; Hong Xin Deng; Han Shuo Yang; Zhimian Li; Zhiyong Li; Li Pan; Fei Leng; Yuquan Wei (Journal of Biosciences, 2010)

Angiotensin-(1–7) and angiotension II in the rostral ventrolateral medulla modulate the cardiac sympathetic afferent reflex and sympathetic activity in rats - Li-Min Zhou; Zhen Shi; Juan Gao; Ying Han; Ning Yuan; Xing-Ya Gao; Guo-Qing Zhu (Pflügers Archiv - European Journal of Physiology, 2010)

Genetic diversity and population structure of 10 Chinese indigenous egg-type duck breeds assessed by microsatellite polymorphism - Hui-Fang Li; Wei-Tao Song; Jing-Ting Shu; Kuan-Wei Chen; Wen-Qi Zhu; Wei Han; Wen-Juan Xu (Journal of Genetics, 2010)

Distribution, development and proliferation of interstitial cells of Cajal in murine colon: an immunohistochemical study from neonatal to adult life - Juan Han; Wen-Hao Shen; You-Zhao Jiang; Bin Yu; Yang-Tao He; Nan Li; Feng Mei (Histochemistry and Cell Biology, 2010)

Identification and characterization of two Bamboo (Phyllostachys praecox) AP1/SQUA-like MADS-box genes during floral transition - Er-Pei Lin; Hua-Zheng Peng; Qun-Ying Jin; Min-Juan Deng; Tao Li; Xin-Chao Xiao; Xi-Qi Hua; Kui-Hong Wang; Hong-Wu Bian; Ning Han; Mu-Yuan Zhu (Planta, 2009)

Expression and purification of bioactive high-purity human midkine in Escherichia coli - Zhong-hui Zhang; Li-juan Du; Di Xiang; Shun-ying Zhu; Ming-yuan Wu; Hui-li Lu; Yan Yu; Wei Han (Journal of Zhejiang University-SCIENCE B, 2009)

An age-dependent proliferation is involved in the postnatal development of interstitial cells of Cajal in the small intestine of mice - Feng Mei; Jiang Zhu; Sheng Guo; De-shan Zhou; Juan Han; Bin Yu; Shi-feng Li; Zhong-yong Jiang; Cheng-jie Xiong (Histochemistry and Cell Biology, 2009)

Comparative analysis of telomeric restriction fragment lengths in different tissues of Ginkgo biloba trees of different age - Di Liu; Nan Qiao; Han Song; Xin Hua; Juan Du; Hai Lu; Fenglan Li (Journal of Plant Research, 2007)

MHC-BPS: MHC-binder prediction server for identifying peptides of flexible lengths from sequence-derived physicochemical properties - Juan Cui; Lian Yi Han; Hong Huang Lin; Zhi Qun Tang; Li Jiang; Zhi Wei Cao; Yu Zong Chen (Immunogenetics, 2006)

Characterization of soybean genomic features by analysis of its expressed sequence tags - Ai-Guo Tian; Jun Wang; Peng Cui; Yu-Jun Han; Hao Xu; Li-Juan Cong; Xian-Gang Huang; Xiao-Ling Wang; Yong-Zhi Jiao; Bang-Jun Wang; Yong-Jun Wang; Jin-Song Zhang; et al. (Theoretical and Applied Genetics, 2004)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)